Light-absorbing anisotropic film, method for producing light-absorbing anisotropic film, laminate, and image display device
By using a light absorption anisotropic film composed of liquid crystal compounds and dichromatic substances in the image display device, the problems of black contrast and tone shift are solved, and efficient light absorption and display effect are achieved.
Patent Information
- Application Number
- CN202380060672.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-04-28
- Filing Date
- 2023-08-15
- Publication Date
- 2025-04-01
AI Technical Summary
In an image display device, it is difficult for the prior art to improve the black contrast and suppress the black tone shift and reflectivity of reflected light when black is displayed.
A light-absorbing anisotropic film containing a liquid crystal compound and a dichromatic substance is used. The dichromatic substance of the film forms an associative compound, and the number of associative compounds having a long axis length of more than 30 nm and less than 60 nm is more than 60 nm, and the orientation and absorption performance of the film are improved by specific manufacturing methods and process parameters, including coating film formation, heating and cooling processes.
The excellent performance of black contrast in the image display device is achieved, the black tone shift is suppressed, and the reflectivity of reflected light is reduced, thereby improving the display effect.
Smart Images

Figure BDA0005277013160000111 
Figure BDA0005277013160000131 
Figure BDA0005277013160000141
Abstract
Description
Technical Field
[0001] The present invention relates to a light absorption anisotropic film, a method for producing the light absorption anisotropic film, a laminate and an image display device. Background Art
[0002] Optically anisotropic layers with phase difference such as λ / 4 plates are used in a wide variety of applications. For example, organic electroluminescent (EL) display devices among image display devices have a structure using metal electrodes, so sometimes they reflect external light, resulting in a decrease in contrast and reflection problems. Therefore, in order to suppress the adverse effects caused by external light reflection, polarizing plates including an optically anisotropic layer and a polarizer (light absorption anisotropic film) have been used.
[0003] Patent Document 1 discloses a circularly polarizing plate formed by laminating a polarizer (light absorption anisotropic film) containing a liquid crystal compound and a dichroic substance and an optical anisotropic layer (λ / 4 plate) containing a liquid crystal compound.
[0004] Previous technical literature
[0005] Patent Literature
[0006] Patent Document 1: International Publication No. 2022-054556 Summary of the invention
[0007] Technical issues to be solved by the invention
[0008] In recent years, image display devices are required to have excellent black contrast in order to further improve image quality. In addition, black contrast means that when the image display device displays black, the color tone shift of black is suppressed and the reflectance of reflected light is low.
[0009] The present inventors have found that when a display device obtained by using a circular polarizing plate as described in Patent Document 1 is set to display black and a display screen is irradiated with visible light, there is room for improvement in black contrast.
[0010] The present invention aims to provide a light absorption anisotropic film which is applied to a display device and has excellent black contrast when the display device is set to black display, a method for producing the light absorption anisotropic film, a laminate and an image display device.
[0011] Means for solving technical problems
[0012] As a result of intensive studies on the problems of the prior art, the present inventors have found that the above-mentioned problems can be solved by the following structure. [1]
[0014] A light absorption anisotropic film comprises a liquid crystal compound and a dichroic substance, wherein:
[0015] The above-mentioned dichroic substance forms a complex. When 100 of the above-mentioned complexes existing on the cross-section of the above-mentioned light absorption anisotropic film observed by a scanning transmission electron microscope are selected, when the number of complexes B whose major axis length is greater than 30 nm and less than 60 nm is set to Nb, and the number of complexes C whose major axis length is greater than 60 nm is set to Nc, the relationship between the above-mentioned Nb and the above-mentioned Nc satisfies the following formula (1).
[0016] Nb>Nc (1) [2]
[0018] The light absorption anisotropic film according to [1], wherein
[0019] The relationship between the above Nb and the above Nc satisfies the following formula (2).
[0020] 0.5×Nb>Nc (2) [3]
[0022] The light absorption anisotropic film according to [1] or [2], wherein
[0023] When 100 aggregates present in the cross section of the light absorption anisotropic film observed by a scanning transmission electron microscope are selected, and when the number of aggregates A having a major axis length of less than 30 nm is defined as Na, Na is 35 or less. [4]
[0025] The light absorption anisotropic film according to any one of [1] to [3], wherein
[0026] The concentration of the dichroic substance in the light absorption anisotropic film is 180 mg / cm 3 above. [5]
[0028] The light absorption anisotropic film according to any one of [1] to [4], wherein
[0029] The absolute value of the difference between the logP value of the liquid crystal compound and the logP value of the dichroic substance is 4.1 or more. [6]
[0031] A method for producing a light-absorbing anisotropic film, which is the method for producing a light-absorbing anisotropic film according to any one of [1] to [5], comprising:
[0032] a coating film forming step of coating a composition including a liquid crystal compound, a dichroic substance and a solvent to form a coating film;
[0033] A first heating step of heating the coating film at a temperature higher than the melting point of the dichroic substance;
[0034] a cooling step of cooling the coating film subjected to the first heating step; and
[0035] The second heating step is to heat the coating film subjected to the cooling step at a temperature that is 15° C. or more lower than the phase transition temperature of the liquid crystal compound from the crystalline state to the liquid crystal state. [7]
[0037] A laminate comprising a substrate and the light absorption anisotropic film according to any one of [1] to [5] disposed on the substrate. [8]
[0039] The laminated body according to [7], further comprising a λ / 4 plate provided on the light absorption anisotropic film. [9]
[0041] An image display device comprising the light absorption anisotropic film according to any one of [1] to [5].
[10]
[0043] An image display device comprising the laminate according to [7] or [8].
[0044] Effects of the Invention
[0045] According to the present invention, a circular polarizing plate combined with a λ / 4 plate is applied to a display device, and a light absorption anisotropic film having excellent black contrast when the display device is set to black display, a method for producing the light absorption anisotropic film, a laminate, and an image display device can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 This is a conceptual diagram showing an example of a state in which the first dichroic substance and the second dichroic substance form an association complex.
[0047] Figure 2 This is a conceptual diagram showing an example of an aggregate of a first dichroic substance and a second dichroic substance.
[0048] Figure 3 This is a diagram schematically showing an example of a cross section of the light absorption anisotropic film of the present invention. DETAILED DESCRIPTION
[0049] Hereinafter, the present invention will be described in detail.
[0050] The description of the constituent elements described below is made based on typical embodiments of the present invention, but the present invention is not limited to these embodiments.
[0051] In addition, in this specification, the numerical range represented by "~" represents a range that includes the numerical values recorded before and after "~" as the lower limit and the upper limit. In the numerical range recorded in stages in this specification, the upper limit or lower limit recorded in a certain numerical range can be replaced by the upper limit or lower limit of the numerical range recorded in other stages. Moreover, in the numerical range recorded in this specification, the upper limit or lower limit recorded in a certain numerical range can also be replaced by the value shown in the embodiment.
[0052] Furthermore, in this specification, parallel, orthogonal, horizontal and vertical respectively represent the range of parallel ±10°, the range of orthogonal ±10°, the range of horizontal ±10° and the range of vertical ±10°, and do not respectively represent parallel, orthogonal, horizontal and vertical in the strict sense.
[0053] In addition, in this specification, for each component, one substance corresponding to each component may be used alone, or two or more substances may be used simultaneously. Here, when two or more substances are used simultaneously for each component, the content of the component refers to the total content of the substances used simultaneously unless otherwise specified.
[0054] Furthermore, in this specification, a combination of two or more preferred aspects is a more preferred aspect.
[0055] Furthermore, in the present specification, “(meth)acrylate” means an expression representing “acrylate” or “methacrylate”, “(meth)acrylic group” means an expression representing “acrylic group” or “methacrylic group”, “(meth)acryloyl” means an expression representing “acryloyl group” or “methacryloyl group”, and “(meth)acrylic acid” means an expression representing “acrylic acid” or “methacrylic acid”.
[0056] [Light absorption anisotropic film]
[0057] The light-absorbing anisotropic film of the present invention comprises a liquid crystal compound and a dichroic substance, wherein the dichroic substance forms an aggregate, and when 100 aggregates existing on a cross section of the light-absorbing anisotropic film observed by a scanning transmission electron microscope are selected, when the number of aggregates B having a major axis length of greater than 30 nm and less than 60 nm is set to Nb, and the number of aggregates C having a major axis length of greater than 60 nm is set to Nc, the relationship between the above Nb and the above Nc satisfies the following formula (1).
[0058] Nb>Nc (1)
[0059] The present inventors have repeatedly studied the relationship between the size of the aggregates contained in the light absorption anisotropic film and the black contrast of the display device, and found that a display device with excellent black contrast can be obtained by satisfying the relationship of formula (1). Although the details of the reason are not clear, it is speculated that by making the number of aggregates with large sizes that are prone to light scattering (the number of aggregates C, Nc) smaller than the number of aggregates B, Nb, light scattering is suppressed and the black contrast of the display device is improved.
[0060] 〔Associated compounds〕
[0061] In the light absorption anisotropic film of the present invention, the dichroic substance forms an association complex.
[0062] Here, the aggregate means a state in which the dichroic substance is aggregated to form an aggregate in the light absorption anisotropic film, and the molecules of the dichroic substance are periodically arranged in the aggregate.
[0063] Furthermore, the association may be formed only of the dichroic substance, or may be formed of the liquid crystal compound and the dichroic substance.
[0064] Furthermore, the association complex may be formed from one dichroic substance or from a plurality of dichroic substances.
[0065] Furthermore, among the aggregates, an aggregate formed of a certain type of dichroic substance and an aggregate formed of another type of dichroic substance may be present in a mixed state in the light absorption anisotropic film.
[0066] Furthermore, when the light absorption anisotropic film contains a plurality of dichroic substances, all or part of the plurality of dichroic substances contained in the light absorption anisotropic film may form an aggregate.
[0067] Figure 1 : is a conceptual diagram showing an example of a state in which the first dichroic substance and the second dichroic substance form an association compound. The light absorption anisotropic film P has molecules M of the first dichroic substance, molecules O of the second dichroic substance, and molecules L of a liquid crystal compound. Figure 1 As shown, an aggregate G including molecules M and molecules O is formed. In the aggregate G, the major axis directions of the molecules M and molecules O are arranged in the same direction, and the molecules M and molecules O are arranged to be staggered at a period of width w.
[0068] The aggregate formed by the first dichroic substance and the second dichroic substance is not limited to Figure 1 The associations, for example, Figure 2 As shown, the molecules M and the molecules O may be arranged to be staggered at a period of an angle a.
[0069] In addition, Figure 1 and Figure 2 In the embodiment, the first dichroic substance and the second dichroic substance may be dichroic substances of the same type or dichroic substances of different types.
[0070] Figure 3 Schematically showing a cross section of an example of the light absorption anisotropic film of the present invention. Figure 3 In the figure, the blank part is the associated compound.
[0071] As a method for verifying that a dichroic substance forms an association, for example, there can be mentioned a method of comparing the maximum absorption wavelength measured using the formed film with the maximum absorption wavelength of a solution.
[0072] Specific examples of methods for measuring the maximum absorption wavelength using the formed film include a method of preparing a thick (10 μm or more) vertically oriented film, cutting the film, and measuring the absorption spectrum of the cross section using an apparatus such as MSV-5200 (manufactured by JASCO Corporation).
[0073] In addition, as a method different from the method of measuring the maximum absorption wavelength using the formed film, there can be mentioned a method of using the composition for forming the light absorption anisotropic film of the present invention without orienting it, and preparing a film formed by the same method as the light absorption anisotropic film of the present invention, and measuring the absorption spectrum of the film. In addition, as a method of not orienting the composition for forming the light absorption anisotropic film, there can be mentioned a method of controlling the orientation by adjusting the presence or absence or amount of an orientation agent or a surface modifier described later, or the presence or absence or change of an orientation film described later.
[0074] Here, when the solution is a sufficiently diluted solution, the maximum absorption wavelength of the solution is considered to be the maximum absorption wavelength of the dichroic substance alone (the dichroic substances do not interact with each other).
[0075] On the other hand, when the maximum absorption wavelength measured using the film is different from the maximum absorption wavelength of the solution, it is considered that the dichroic substance interacts with the other substance (that is, forms an association complex).
[0076] Specifically, the maximum absorption wavelength λs in the absorption spectrum of the solution in which the dichroic substance is dissolved is determined. In this case, the concentration of the diluted solution is preferably 3.0% or less, and more preferably 2.0% or less.
[0077] Next, a composition containing at least a liquid crystal compound and a dichroic substance is cast onto a substrate (e.g., blue plate glass), and cured by heating and ultraviolet irradiation in the same manner as the light absorption anisotropic film of the present invention to form a film F for measuring the maximum absorption wavelength. Then, the absorption spectrum of the film F is measured at a 0.5 nm pitch within a wavelength range of 380 to 800 nm to determine the maximum absorption wavelength λf.
[0078] From the reasons described below, it is understood that the dichroic substance forms an association complex when the above-mentioned λs and λf satisfy the following formula (D).
[0079] |λs-λf|≥2.0nm (D)
[0080] That is, the absorption spectrum of the solution formed by dissolving the dichroic substance is understood as the absorption spectrum in one molecule of the dichroic substance. Therefore, when the maximum absorption wavelength λs of the absorption spectrum and the maximum absorption wavelength λf of the absorption spectrum of film F satisfy the above formula (D), it can be said that in film F, the maximum absorption wavelength has shifted due to the association of the dichroic substance.
[0081] In the present invention, when observing a cross section with a scanning transmission electron microscope (Scanning Transmission Electron Microscope) (hereinafter, also referred to as "STEM"), it is specifically performed as follows.
[0082] First, an ultrathin slice having a thickness of more than 100 nm is prepared from the light absorption anisotropic film along the film thickness direction using an ultrathin slicer.
[0083] Next, the ultrathin sections were placed on a grid with a carbon support film for STEM observation.
[0084] Thereafter, each grid was placed in a scanning transmission electron microscope, and a cross section was observed at an electron beam acceleration voltage of 30 kV.
[0085] Furthermore, the length L of the major axis and the length D of the minor axis of the aggregate are specifically measured as follows.
[0086] First, as described above, a cross section of the light absorption anisotropic film is observed by STEM, the image taken is analyzed, a frequency histogram is prepared, and the frequency at which the frequency becomes the maximum and the standard deviation of the frequency distribution are obtained. Next, the frequency at which the frequency becomes the maximum to the dark side becomes 1.3 times the standard deviation is set as a threshold. Next, an image is prepared in which the brightness is binarized using this threshold, and the portion with a major axis of 10 nm or more in the binarized dark region is extracted as an association.
[0087] In addition, each extracted aggregate is approximated by an ellipse, and the length of the major axis of the approximated ellipse is set as the length of the major axis of the aggregate L, and the length of the minor axis of the approximated ellipse is set as the length of the minor axis of the aggregate D. Furthermore, the angle formed by the axis perpendicular to the film surface (the normal direction of the light absorption anisotropic film) and the major axis of the approximated ellipse is set as the angle formed by the major axis of the aggregate and the normal direction of the light absorption anisotropic film.
[0088] The length L of the major axis and the length D of the minor axis of the aggregate may be measured using known image processing software. As the image processing software, for example, the image processing software "ImageJ" can be exemplified.
[0089] In the light absorption anisotropic film of the present invention, when any 100 aggregates present in an image obtained by analyzing a cross-sectional image taken by STEM are selected, the relationship between the number Nb of aggregates B having a major axis length L of 30 nm or more and less than 60 nm and the number Nc of aggregates C having a major axis length L of 60 nm or more satisfies the following formula (1). In view of a better black contrast ratio of the image display device, it is preferred to satisfy the following formula (2).
[0090] Nb>Nc (1)
[0091] 0.5×Nb>Nc (2)
[0092] Specifically, the image analysis described above was performed, and the 13.58 μm 2 area, 3 locations (40 μm in total) 2 ), select any 100 aggregates satisfying L ≥ 10 nm. 2 ) in the region satisfying L ≥ 10 nm is less than 100, until the number reaches 100, further from other regions (13.58 μm per site) 2 )Select the complex satisfying L≥10nm.
[0093] In the arbitrarily selected non-overlapping 40 μm 2 (13.58μm 2 ×3) and 10 sites, and the number of associates B and associates C is counted for each site. On this basis, the average value of the number of associates B and the average value of the number of associates C in the 10 sites measured are calculated, and the average values are set as the number of associates B Nb and the number of associates C Nc, respectively.
[0094] In fact, the measured value is 13.58 μm. 2×3=40.74μm 2 However, in the present invention, for the sake of convenience, the decimal point is discarded and referred to as "every 40 μm 2 ”.
[0095] From the viewpoint of achieving a better black contrast ratio in an image display device, the number Nb of the associations B is preferably 50 or more, and more preferably 60 or more.
[0096] The upper limit of the number Nb of the associates B is not particularly limited, but is usually 100 or less, often 99 or less, and more often 90 or less.
[0097] From the viewpoint of achieving a better black contrast ratio in an image display device, the number Nc of the association complexes C is preferably 40 or less, and more preferably 20 or less.
[0098] As a method of adjusting the number Nb and the number Nc so as to satisfy the above-mentioned formula (1), for example, there is a method of using a method for producing a light absorption anisotropic film described later.
[0099] Furthermore, as a method for adjusting the number Nb and the number Nc so as to satisfy the above formula (2), for example, there can be cited a method of using a dichroic substance and a liquid crystal composition that satisfy the ΔlogP described later and a method of adjusting the concentration of the dichroic substance in the light absorption anisotropic film to the range described later.
[0100] In the light absorption anisotropic film of the present invention, when any 100 aggregates present in an image obtained by analyzing a cross-sectional image photographed by STEM are selected, the number Na of aggregates A having a major axis length L of less than 30 nm is preferably 35 or less, and more preferably less than 20. When the number Na of aggregates A is 35 or less, the heat resistance is excellent.
[0101] The number Na of aggregates A was determined in the same manner as the number Nb of aggregates B and the number Nc of aggregates C, except that the number of aggregates having a major axis length L of less than 30 nm was counted.
[0102] As a method for adjusting the number Na to the above range, for example, there can be cited a method of adopting the method for producing the light absorption anisotropic film described later, using a dichroic substance and a liquid crystal composition satisfying the ΔlogP described later, and adjusting the concentration of the dichroic substance in the light absorption anisotropic film to the range described later, etc. Furthermore, the number Na can also be adjusted according to the heating temperature in the method for producing the light absorption anisotropic film described later. For example, if the second heating temperature becomes higher, the value of the number Na becomes smaller.
[0103] 〔Liquid crystal compounds〕
[0104] The light absorption anisotropic film of the present invention contains a liquid crystal compound, thereby suppressing the precipitation of the dichroic substance and aligning the dichroic substance with a higher degree of orientation.
[0105] As the liquid crystal compound, any of a high molecular weight liquid crystal compound and a low molecular weight liquid crystal compound can be used, and a high molecular weight liquid crystal compound is more preferred from the viewpoint of being able to improve the degree of orientation. Furthermore, as the liquid crystal compound, a high molecular weight liquid crystal compound and a low molecular weight liquid crystal compound can be used simultaneously.
[0106] Here, the "polymer liquid crystal compound" refers to a liquid crystal compound having a repeating unit in its chemical structure.
[0107] Furthermore, the “low-molecular liquid crystal compound” refers to a liquid crystal compound having no repeating unit in its chemical structure.
[0108] Examples of the polymer liquid crystal compound include the thermotropic liquid crystal polymer described in JP-A-2011-237513 and the polymer liquid crystal compound described in paragraphs
[0012] to
[0042] of WO-2018 / 199096.
[0109] Examples of the low-molecular liquid crystal compound include the liquid crystal compounds described in paragraphs
[0072] to
[0088] of JP-A-2013-228706, and among these, liquid crystal compounds showing smecticity are preferred.
[0110] Examples of such liquid crystal compounds include those described in paragraphs
[0019] to
[0140] of International Publication No. 2022 / 014340, and these descriptions are incorporated into this specification by reference.
[0111] From the viewpoint of achieving more excellent effects of the present invention, the content of the liquid crystal compound is preferably 50 to 99% by mass, more preferably 65 to 85% by mass, based on the total mass of the light absorption anisotropic film.
[0112] The logP value of the liquid crystal compound is preferably 3.5 to 8.5, more preferably 4.5 to 7.5.
[0113] Here, the logP value is an index of the hydrophilicity and hydrophobicity of the chemical structure, and is sometimes referred to as a hydrophilic parameter. The logP value of each compound in this specification can be calculated using software such as ChemBioDraw Ultra or HSPiP (Ver.4.1.07). In addition, it can also be obtained by experiment using the method of OECD Guidelines for the Testing of Chemicals, Sections 1, Test No.117, etc. In the present invention, unless otherwise specified, the value calculated by entering the structural formula of the compound in HSPiP (Ver.4.1.07) is used as the logP value.
[0114] 〔Dichroic substances〕
[0115] The light absorption anisotropic film of the present invention contains a dichroic substance.
[0116] The dichroic substance is preferably a dichroic azo dye compound, and dichroic azo dye compounds generally used in so-called coating type polarizers can be used. The dichroic azo dye compound is not particularly limited, and conventionally known dichroic azo dyes can be used, but the compounds described below are preferably used.
[0117] In the light absorbing anisotropic film, the dichroic substance may be polymerized.
[0118] In the present invention, the dichroic azo dye compound refers to a dye whose absorbance differs depending on the direction.
[0119] The dichroic azo dye compound may or may not exhibit liquid crystallinity.
[0120] When the dichroic azo dye compound exhibits liquid crystallinity, it may exhibit either nematicity or smecticity. The temperature range for exhibiting the liquid crystal phase is preferably room temperature (about 20°C to 28°C) to 300°C, and more preferably 50°C to 200°C from the viewpoint of operability and manufacturing suitability.
[0121] In the present invention, from the viewpoint of adjusting the color tone, the light absorption anisotropic film preferably has at least one pigment compound having a maximum absorption wavelength in the wavelength range of 560 to 700 nm (hereinafter, also referred to as the "first dichroic azo pigment compound") and at least one pigment compound having a maximum absorption wavelength in the wavelength range of 455 nm to less than 560 nm (hereinafter, also referred to as the "second dichroic azo pigment compound"), and specifically, it is more preferred to have at least a dichroic azo pigment compound represented by formula (1) described later and a dichroic azo pigment compound represented by formula (2) described later.
[0122] In the present invention, three or more dichroic azo dye compounds may be used simultaneously. For example, from the viewpoint of making the light absorption anisotropic film close to black, it is preferred to simultaneously use a first dichroic azo dye compound, a second dichroic azo dye compound, and at least one dye compound having a maximum absorption wavelength in a range of wavelengths greater than 380 nm and less than 455 nm (preferably a range of wavelengths of 380 to 454 nm) (hereinafter also referred to as "the third dichroic azo dye compound").
[0123] In the present invention, the dichroic azo dye compound preferably has a crosslinkable group because the pressure resistance is further improved.
[0124] Specific examples of the crosslinkable group include a (meth)acryloyl group, an epoxy group, an oxetanyl group, and a styryl group. Among them, a (meth)acryloyl group is preferred.
[0125] <The first dichroic azo dye compound>
[0126] The first dichroic azo dye compound is preferably a compound having a chromophore as a core and a side chain bonded to the terminal of the chromophore.
[0127] Specific examples of the chromophore include aromatic ring groups (e.g., aromatic hydrocarbon groups, aromatic heterocyclic groups), azo groups, and the like. Preferably, the chromophore has a structure having both an aromatic ring group and an azo group, and more preferably, a disazo structure having an aromatic heterocyclic group (preferably a thienothiazolyl group) and two azo groups.
[0128] The side chain is not particularly limited, and examples thereof include groups represented by L3, R2 or L4 in the formula (1) described later.
[0129] From the viewpoint of adjusting the color tone of the light absorption anisotropic film, the first dichroic azo dye compound preferably has a maximum absorption wavelength in the range of 560 nm to 700 nm (more preferably 560 to 650 nm, and even more preferably 560 to 640 nm).
[0130] The maximum absorption wavelength (nm) of the dichroic azo dye compound in the present specification is determined from an ultraviolet-visible spectrum in the wavelength range of 380 to 800 nm measured by a spectrophotometer using a solution prepared by dissolving the dichroic azo dye compound in a good solvent.
[0131] In the present invention, the first dichroic azo dye compound is preferably a compound represented by the following formula (1) because the degree of orientation of the formed light absorption anisotropic film is further improved.
[0132] When the dichroic material includes a compound represented by the following formula (1), the degree of orientation of the light absorption anisotropic film is further improved, presumably because the interactions between the first dichroic azo dyes and between the first dichroic azo dyes and the liquid crystal compound are enhanced.
[0133] [Chemical formula 1]
[0134]
[0135] In the formula (1), Ar1 and Ar2 each independently represent a phenylene group which may have a substituent or a naphthylene group which may have a substituent, and a phenylene group is preferred.
[0136] In formula (1), R1 represents a hydrogen atom, or an alkyl group, an alkoxy group, an alkylthio group, an alkylsulfonyl group, an alkylcarbonyl group, an alkoxycarbonyl group, an acyloxy group, an alkyl carbonate group, an alkylamino group, an acylamino group, an alkylcarbonylamino group, an alkoxycarbonylamino group, an alkylsulfonylamino group, an alkylsulfonyl group, an alkylamino group, an alkylcarbamoyl group, an alkylsulfinyl group, an alkylurea group, an alkylphosphoric acid amide group, an alkylimino group or an alkylsilyl group which may have a substituent.
[0137] When R1 is a group containing carbon atoms, the number of carbon atoms in R1 is preferably 1 or more, more preferably 3 or more, further preferably 5 or more, particularly preferably 9 or more, and most preferably 10 or more from the viewpoint of better orientation.
[0138] When R1 is a group containing carbon atoms, the number of carbon atoms in R1 is preferably 20 or less, more preferably 18 or less, and further preferably 15 or less.
[0139] When R1 is an alkyl group or a group containing an alkyl group, the alkyl group may be linear or branched.
[0140] When R1 is an alkyl group, the -CH2- in the alkyl group may be substituted by a divalent substituent such as -O-, -CO-, -C(O)-O-, -OC(O)-, -Si(CH3)2-O-Si(CH3)2-, -N(R1')-, -N(R1')-CO-, -CO-N(R1')-, -N(R1')-C(O)-O-, -OC(O)-N(R1')-, -N(R1')-C(O)-N(R1')-, -CH=CH-, -C≡C-, -N=N-, -C(R1')=CH-C(O)-, -OC(O)-O-, and the like. Among these divalent substituents, -O-, -CO-, -C(O)-O- or -OC(O)- is preferred.
[0141] When R1 is a group other than a hydrogen atom, specific examples of substituents (monovalent substituents) that each group may have are described below, among which preferred are acyl, acyloxy, halogen, nitro, cyano, -N(R1')2, amino, -C(R1')=C(R1')-NO2, -C(R1')=C(R1')-CN, or -C(R1')=C(CN)2.
[0142] R1' represents a hydrogen atom or a linear or branched alkyl group having 1 to 6 carbon atoms. In each group, when a plurality of R1's exist, they may be the same as or different from each other.
[0143] In formula (1), R2 and R3 each independently represent a hydrogen atom, or an alkyl group, an alkoxy group, an acyl group, an alkoxycarbonyl group, an alkylamide group, an alkylsulfonyl group, an aryl group, an arylcarbonyl group, an arylsulfonyl group, an aryloxycarbonyl group or an arylamide group which may have a substituent.
[0144] When R2 or R3 is an alkyl group, the -CH2- in the alkyl group may be substituted by a divalent substituent such as -O-, -S-, -C(O)-, -C(O)-O-, -OC(O)-, -C(O)-S-, -SC(O)-, -Si(CH3)2-O-Si(CH3)2-, -NR2'-, -NR2'-CO-, -CO-NR2'-, -NR2'-C(O)-O-, -OC(O)-NR2'-, -NR2'-C(O)-NR2'-, -CH=CH-, -C≡C-, -N=N-, -C(R2')=CH-C(O)-, or -OC(O)-O-.
[0145] When R2 and R3 are groups other than hydrogen atoms, specific examples of substituents (monovalent substituents) that each group may have are described below, among which preferred are halogen atoms, nitro groups, cyano groups, hydroxyl groups, -N(R2')2, amino groups, -C(R2')=C(R2')-NO2, -C(R2')=C(R2')-CN, or -C(R2')=C(CN)2.
[0146] R2' represents a hydrogen atom or a linear or branched alkyl group having 1 to 6 carbon atoms. In each group, when a plurality of R2' exist, they may be the same as or different from each other.
[0147] R2 and R3 may be bonded to each other to form a ring, and R2 or R3 may be bonded to Ar2 to form a ring.
[0148] From the viewpoint of light resistance, R1 is preferably an electron-withdrawing group, and R2 and R3 are preferably groups with low electron-donating properties.
[0149] Specific examples of such groups include, as R1, alkylsulfonyl, alkylcarbonyl, alkoxycarbonyl, acyloxy, alkylsulfonylamino, alkylsulfamoyl, alkylsulfinyl and alkylureido, and as R2 and R3, groups of the following structures, etc. In addition, the groups of the following structures are represented in the above formula (1) in the form of containing the nitrogen atom to which R2 and R3 are bonded.
[0150] [Chemical formula 2]
[0151]
[0152] Specific examples of the first dichroic azo dye compound are shown below, but the present invention is not limited to these.
[0153] [Chemical formula 3]
[0154]
[0155]
[0156] <Second dichroic azo dye compound>
[0157] The second dichroic azo dye compound is a compound different from the first dichroic azo dye compound, and specifically, the chemical structure thereof is different.
[0158] The second dichroic azo dye compound is preferably a compound having a chromophore as a core of the dichroic azo dye compound and a side chain bonded to the terminal of the chromophore.
[0159] Specific examples of the chromophore include aromatic ring groups (e.g., aromatic hydrocarbon groups, aromatic heterocyclic groups), azo groups, etc., preferably a structure having both an aromatic hydrocarbon group and an azo group, more preferably a disazo or trisazo structure having an aromatic hydrocarbon group and two or three azo groups.
[0160] The side chain is not particularly limited, and examples thereof include groups represented by R4, R5 or R6 in the formula (2) described later.
[0161] The second dichroic azo dye compound is a dichroic azo dye compound having a maximum absorption wavelength in the range of wavelengths greater than 455 nm and less than 560 nm. From the viewpoint of adjusting the color tone of the light absorption anisotropic film, it is preferably a dichroic azo dye compound having a maximum absorption wavelength in the range of wavelengths of 455 to 555 nm, and more preferably a dichroic azo dye compound having a maximum absorption wavelength in the range of wavelengths of 455 to 550 nm.
[0162] In particular, by using a first dichroic azo dye compound having a maximum absorption wavelength of 560 to 700 nm and a second dichroic azo dye compound having a maximum absorption wavelength of 455 nm to less than 560 nm, it is easier to adjust the color tone of the light absorption anisotropic film.
[0163] From the viewpoint of further improving the degree of orientation of the light absorption anisotropic film, the second dichroic azo dye compound is preferably a compound represented by formula (2).
[0164] [Chemical formula 4]
[0165]
[0166] In formula (2), n represents 1 or 2.
[0167] In the formula (2), Ar3, Ar4 and Ar5 each independently represent a phenylene group which may have a substituent, a naphthylene group which may have a substituent, or a heterocyclic group which may have a substituent.
[0168] The heterocyclic group may be either aromatic or non-aromatic.
[0169] Examples of atoms other than carbon constituting the aromatic heterocyclic group include a nitrogen atom, a sulfur atom, and an oxygen atom. When the aromatic heterocyclic group has a plurality of atoms other than carbon constituting the ring, these atoms may be the same or different.
[0170] Specific examples of the aromatic heterocyclic group include, for example, a pyridylene group (pyridine-diyl), a pyridazine-diyl group, an imidazole-diyl group, a thiophene-diyl group (thiophene-diyl group), a quinolylene group (quinoline-diyl group), an isoquinolylene group (isoquinoline-diyl group), an oxazole-diyl group, a thiazole-diyl group, an oxadiazole-diyl group, a benzothiazole-diyl group, a benzothiadiazole-diyl group, a phthalimide-diyl group, a thienothiazole-diyl group, a thiazolothiazole-diyl group, a thienothiophene-diyl group and a thienothiazole-diyl group.
[0171] In formula (2), R4 has the same definition as R1 in formula (1).
[0172] In formula (2), R5 and R6 have the same definitions as R2 and R3 in formula (1), respectively.
[0173] From the viewpoint of light resistance, R4 is preferably an electron-withdrawing group, and R5 and R6 are preferably groups with low electron-donating properties.
[0174] In this group, specific examples when R4 is an electron withdrawing group are the same as those when R1 is an electron withdrawing group, and specific examples when R5 and R6 are groups with low electron donating property are the same as those when R2 and R3 are groups with low electron donating property.
[0175] Specific examples of the second dichroic azo dye compound are shown below, but the present invention is not limited thereto.
[0176] [Chemical formula 5]
[0177]
[0178]
[0179]
[0180]
[0181] <Third dichroic azo dye compound>
[0182] The third dichroic azo dye compound is a dichroic azo dye compound other than the first dichroic azo dye compound and the second dichroic azo dye compound, and specifically, its chemical structure is different from the chemical structure of the first dichroic azo dye compound and the second dichroic azo dye compound. If the light absorption anisotropic film contains the third dichroic azo dye compound, there is an advantage that the color tone of the light absorption anisotropic film can be easily adjusted.
[0183] The maximum absorption wavelength of the third dichroic azo dye compound is 380 nm or more and less than 455 nm, preferably 385 to 454 nm.
[0184] Specific examples of the third dichroic azo dye compound include compounds represented by formula (1) described in International Publication No. 2017 / 195833. Among the compounds, compounds other than the first dichroic azo dye compound and the second dichroic azo dye compound may be mentioned.
[0185] Specific examples of the third dichroic azo dye compound are shown below, but the present invention is not limited to these. In the following specific examples, n represents an integer of 1 to 10. Furthermore, Me represents a methyl group.
[0186] [Chemical formula 6]
[0187]
[0188] [Chemical formula 7]
[0189]
[0190] (Content of dichroic substances)
[0191] The concentration of the dichroic substance in the light absorption anisotropic film is preferably 170 mg / cm 3 More preferably 180 mg / cm3 More preferably, 240 mg / cm 3 above.
[0192] If the concentration of dichroic material is 180 mg / cm 3 Above, the number Nb of the complexes B whose major axis length is greater than 30nm and less than 60nm is greater than the number Nc of the complexes C whose major axis length is greater than 60nm. Although the details of the reason are not clear, it is speculated to be due to the following reasons. For example, it is believed that when the content of the dichroic substance in the composition used in forming the light absorbing anisotropic film is high, the number of nuclei generated for forming the complexes of the dichroic substance increases when the light absorbing anisotropic film is formed. In this way, if the number of nuclei in the film increases, the number of molecules of the dichroic substance that are not used for the formation of the nuclei decreases, thereby suppressing the increase in the size of the complex. As a result, it is speculated that the number of small-sized complexes such as the complex B increases.
[0193] The concentration of the dichroic substance in the light absorption anisotropic film is preferably 500 mg / cm 3 Below, more preferably 400 mg / cm 3 Below, more preferably 300 mg / cm 3 If the concentration of dichroic material is 500mg / cm 3 Below, the pigment precipitation in the film can be suppressed.
[0194] Here, the concentration of the dichroic substance in the light absorption anisotropic film can be determined by measuring a solution obtained by dissolving the light absorption anisotropic film or an extract obtained by immersing the light absorption anisotropic film in a solvent using high-speed liquid chromatography (HPLC). In addition, quantification can be performed by using the dichroic substance contained in the light absorption anisotropic film as a standard sample.
[0195] In addition, when the HPLC measurement is performed using a laminate having a light absorption anisotropic film, the concentration of the dichroic substance in the light absorption anisotropic film can be calculated as follows. First, the volume is calculated by multiplying the thickness of the light absorption anisotropic film obtained from a microscopic observation image of a cross section of the laminate by the area of the laminate used for the HPLC measurement. Then, the concentration of the dichroic substance in the light absorption anisotropic film is obtained by dividing the mass of the dichroic substance measured by HPLC by the obtained volume.
[0196] The content of the dichroic substance is preferably 17 to 50% by mass, more preferably 23 to 30% by mass, based on the total mass of the light absorption anisotropic film.
[0197] The content of the first dichroic azo dye compound is preferably 40 to 90 parts by mass, more preferably 45 to 85 parts by mass, based on 100 parts by mass of the total content of the dichroic substances in the light absorption anisotropic film.
[0198] The content of the second dichroic azo dye compound is preferably 4 to 50 parts by mass, more preferably 5 to 35 parts by mass, based on 100 parts by mass of the entire content of the dichroic substances in the light absorption anisotropic film.
[0199] The content of the third dichroic azo dye compound is preferably 1 to 50 parts by mass, more preferably 2 to 40 parts by mass, based on 100 parts by mass of the entire content of the dichroic substances in the light absorption anisotropic film.
[0200] The content ratio of the first dichroic azo dye compound, the second dichroic azo dye compound, and the third dichroic azo dye compound used as needed can be arbitrarily set to adjust the color tone of the light absorption anisotropic film. Among them, the content ratio of the second dichroic azo dye compound to the first dichroic azo dye compound (the second dichroic azo dye compound / the first dichroic azo dye compound) is preferably 0.1 to 10, more preferably 0.2 to 5, and further preferably 0.3 to 0.8 in terms of mole conversion. As long as the content ratio of the second dichroic azo dye compound to the first dichroic azo dye compound is within the above range, the orientation degree can be improved.
[0201] <logP value>
[0202] The absolute value of the difference between the logP value of the liquid crystal compound and the logP value of the dichroic substance (hereinafter also referred to as “ΔlogP”) is preferably 4.1 or more, more preferably 5.1 or more, and even more preferably 6.1 or more.
[0203] If ΔlogP is 4.1 or more, the number Nb of the associates B whose major axis length is 30 nm or more and less than 60 nm can be made greater than the number Nc of the associates C whose major axis length is 60 nm or more. Although the details of the reason are not clear, it is speculated to be due to the following reasons. It is believed that if the difference between the logP value of the liquid crystal compound and the logP value of the dichroic substance becomes larger, the compatibility of the two components decreases, thereby promoting the generation of the nucleus of the associates for forming the dichroic substance. It is believed that if the generation of the nucleus in the film is promoted and the number thereof increases, the number of molecules of the dichroic substance that is not used for the formation of the nucleus in the film decreases. Therefore, it is speculated that the number of small-sized associates such as the associate B increases due to the suppression of the increase in the size of the associate.
[0204] From the viewpoint of solubility, ΔlogP is preferably 9.0 or less, more preferably 8.0 or less, and even more preferably 7.0 or less.
[0205] In addition, when the light absorption anisotropic film contains multiple dichroic substances or liquid crystal compounds, among the absolute values of the differences calculated from the logP values of the dichroic substances and the logP values of the liquid crystal compounds, it is sufficient that the maximum value satisfies the above-mentioned ΔlogP value, but from the perspective of better black contrast, it is preferred that all values satisfy the above-mentioned value.
[0206] The logP value of the dichroic substance is preferably 8-13, more preferably 8.5-12.5, and even more preferably 9-12.
[0207] In addition, the method for measuring the LogP value of the dichroic substance is as described above.
[0208] [Other ingredients]
[0209] The light absorption anisotropic film of the present invention may contain components other than the liquid crystal compound and the dichroic substance (hereinafter also referred to as “other components”).
[0210] Specific examples of other components include surface improvers and the like.
[0211] <Surface Improver>
[0212] The light absorbing anisotropic film of the present invention preferably contains a surface modifier (hereinafter also referred to as a "surfactant"). By containing a surface modifier, it is expected that the smoothness of the coating surface will be improved, the degree of orientation will be improved, or the in-plane uniformity will be improved by suppressing pits and unevenness.
[0213] As a surface modifier, a surface modifier that horizontally aligns the liquid crystal compound is preferred, and the compounds (horizontal alignment agents) described in paragraphs
[0253] to
[0293] of Japanese Patent Publication No. 2011-237513 can be used. In addition, fluoro(meth)acrylate polymers described in paragraphs
[0018] to
[0043] of Japanese Patent Publication No. 2007-272185 can be used. As a surface modifier, compounds other than these can also be used. One type of surface modifier can be used alone, or two or more types can be used simultaneously.
[0214] The weight average molecular weight of the surface modifier is preferably 5,000 to 30,000, more preferably 5,000 to 17,500.
[0215] When the light absorption anisotropic film contains a surface modifier, the content of the surface modifier is preferably 0.1 to 2.0% by mass, more preferably 0.1 to 1.0% by mass, based on the total mass of the light absorption anisotropic film.
[0216] Here, the weight average molecular weight in the present invention is a value measured by gel permeation chromatography (GPC) under the following conditions.
[0217] Solvent (eluent): N-methylpyrrolidone
[0218] Device name: TOSOH HLC-8220GPC
[0219] Column: 3 TOSOH TSKgelSuperAWM-H (6mm×15cm) connected and used
[0220] Column temperature: 25℃
[0221] Sample concentration: 0.1 mass%
[0222] Flow rate: 0.35ml / min
[0223] Calibration curve: Calibration curve of seven samples with Mw=2800000 to 1050 (Mw / Mn=1.03 to 1.06) based on TSK standard polystyrene manufactured by TOSOH
[0224] 〔Substituent〕
[0225] Unless otherwise specified, the substituent (monovalent substituent) in the present specification means the following groups.
[0226] As the substituent, for example,
[0227] Alkyl (preferably an alkyl group having 1 to 20 carbon atoms, more preferably an alkyl group having 1 to 12 carbon atoms, and still more preferably an alkyl group having 1 to 8 carbon atoms, for example, methyl, ethyl, isopropyl, tert-butyl, n-octyl, n-decyl, n-hexadecyl, cyclopropyl, cyclopentyl, and cyclohexyl);
[0228] alkenyl (preferably an alkenyl group having 2 to 20 carbon atoms, more preferably an alkenyl group having 2 to 12 carbon atoms, and still more preferably an alkenyl group having 2 to 8 carbon atoms, for example, vinyl, aryl, 2-butenyl, and 3-pentenyl);
[0229] Alkynyl (preferably an alkynyl group having 2 to 20 carbon atoms, more preferably an alkynyl group having 2 to 12 carbon atoms, and still more preferably an alkynyl group having 2 to 8 carbon atoms, for example, propargyl and 3-pentynyl, etc.);
[0230] Aryl group (preferably an aryl group having 6 to 30 carbon atoms, more preferably an aryl group having 6 to 20 carbon atoms, and still more preferably an aryl group having 6 to 12 carbon atoms, for example, phenyl, 2,6-diethylphenyl, 3,5-ditrifluoromethylphenyl, styryl, naphthyl, and biphenyl);
[0231] a substituted or unsubstituted amino group (preferably an amino group having 0 to 20 carbon atoms, more preferably an amino group having 0 to 10 carbon atoms, and still more preferably an amino group having 0 to 6 carbon atoms, for example, an unsubstituted amino group, a methylamino group, a dimethylamino group, a diethylamino group, and an anilino group);
[0232] Alkoxy group (preferably having 1 to 20 carbon atoms, more preferably having 1 to 15 carbon atoms, for example, methoxy, ethoxy, butoxy, etc.);
[0233] Oxycarbonyl (preferably having 2 to 20 carbon atoms, more preferably 2 to 15 carbon atoms, and still more preferably 2 to 10 carbon atoms, for example, methoxycarbonyl, ethoxycarbonyl, and phenoxycarbonyl);
[0234] acyl group (preferably an acyl group having 1 to 48 carbon atoms, more preferably an acyl group having 1 to 24 carbon atoms, for example, formyl, acetyl, acryloyl, methacryloyl, pivaloyl, benzoyl, tetradecanoyl, cyclohexanoyl);
[0235] an acyloxy group (preferably having 2 to 20 carbon atoms, more preferably 2 to 10 carbon atoms, and still more preferably 2 to 6 carbon atoms, for example, an acetoxy group, a benzoyloxy group, an acryloyloxy group, and a methacryloyloxy group);
[0236] Acylamino group (preferably having 2 to 20 carbon atoms, more preferably having 2 to 10 carbon atoms, and still more preferably having 2 to 6 carbon atoms, for example, acetylamino group and benzylamino group);
[0237] an alkoxycarbonylamino group (preferably having 2 to 20 carbon atoms, more preferably 2 to 10 carbon atoms, and still more preferably 2 to 6 carbon atoms, for example, a methoxycarbonylamino group, etc.);
[0238] An aryloxycarbonylamino group (preferably having 7 to 20 carbon atoms, more preferably 7 to 16 carbon atoms, and still more preferably 7 to 12 carbon atoms, for example, a phenoxycarbonylamino group, etc.);
[0239] Sulfonylamino group (preferably having 1 to 20 carbon atoms, more preferably having 1 to 10 carbon atoms, and still more preferably having 1 to 6 carbon atoms, for example, methanesulfonylamino group and benzenesulfonylamino group);
[0240] A sulfamoyl group (preferably having 0 to 20 carbon atoms, more preferably having 0 to 10 carbon atoms, and still more preferably having 0 to 6 carbon atoms, examples of which include a sulfamoyl group, a methylsulfamoyl group, a dimethylsulfamoyl group, and a phenylsulfamoyl group);
[0241] Carbamoyl (preferably having 1 to 20 carbon atoms, more preferably 1 to 10 carbon atoms, and still more preferably 1 to 6 carbon atoms, for example, unsubstituted carbamoyl, methylcarbamoyl, diethylcarbamoyl, and phenylcarbamoyl);
[0242] an alkylthio group (preferably having 1 to 20 carbon atoms, more preferably 1 to 10 carbon atoms, and still more preferably 1 to 6 carbon atoms, for example, methylthio and ethylthio);
[0243] an arylthio group (preferably having 6 to 20 carbon atoms, more preferably 6 to 16 carbon atoms, and still more preferably 6 to 12 carbon atoms, for example, a phenylthio group, etc.);
[0244] Sulfonyl group (preferably having 1 to 20 carbon atoms, more preferably having 1 to 10 carbon atoms, and still more preferably having 1 to 6 carbon atoms, for example, methanesulfonyl and toluenesulfonyl);
[0245] Sulfinyl group (preferably having 1 to 20 carbon atoms, more preferably 1 to 10 carbon atoms, and still more preferably 1 to 6 carbon atoms, for example, methanesulfinyl group and benzenesulfinyl group);
[0246] A urea group (preferably having 1 to 20 carbon atoms, more preferably 1 to 10 carbon atoms, and still more preferably 1 to 6 carbon atoms, for example, an unsubstituted urea group, a methyl urea group, and a phenyl urea group);
[0247] A phosphoric acid amide group (preferably having 1 to 20 carbon atoms, more preferably 1 to 10 carbon atoms, and still more preferably 1 to 6 carbon atoms, for example, a diethyl phosphoric acid amide group and a phenyl phosphoric acid amide group, etc. can be mentioned);
[0248] Halogen atoms (e.g., fluorine atom, chlorine atom, bromine atom, and iodine atom);
[0249] a heteroatom-containing cyclic group (preferably a heteroatom-containing cyclic group having 1 to 30 carbon atoms, more preferably a heteroatom-containing cyclic group having 1 to 12 carbon atoms, for example, a heteroatom-containing cyclic group having a heteroatom such as a nitrogen atom, an oxygen atom, or a sulfur atom, for example, an epoxy group, an oxetanyl group, an imidazolyl group, a pyridyl group, a quinolyl group, a furanyl group, a piperidinyl group, a morpholinyl group, a maleimide group, a benzoxazolyl group, a benzimidazolyl group, and a benzothiazolyl group);
[0250] Silyl group (preferably a silyl group having 3 to 40 carbon atoms, more preferably a silyl group having 3 to 30 carbon atoms, and still more preferably a silyl group having 3 to 24 carbon atoms, for example, trimethylsilyl group and triphenylsilyl group);
[0251] Hydroxyl; mercapto; cyano; nitro; hydroxamic acid; sulfinyl; hydrazine; imino; azo; carboxyl; sulfonic acid; phosphate; etc.
[0252] [Light-absorbing anisotropic film-forming composition]
[0253] The light absorption anisotropic film of the present invention is preferably formed using a light absorption anisotropic film-forming composition containing a liquid crystal compound and a dichroic substance.
[0254] The light absorption anisotropic film-forming composition preferably contains a polymerization initiator, a solvent, and the like in addition to the liquid crystal compound and the dichroic substance, and may contain the other components described above.
[0255] The liquid crystal compound and the dichroic substance contained in the light absorption anisotropic film-forming composition are respectively the same as the liquid crystal compound and the dichroic substance contained in the light absorption anisotropic film of the present invention.
[0256] The contents of the liquid crystal compound and the dichroic substance relative to the total solid content of the light absorption anisotropic film-forming composition are preferably the same as the contents of the liquid crystal compound and the dichroic substance relative to the total mass of the light absorption anisotropic film of the present invention.
[0257] Here, the “total solid content in the light absorption anisotropic film-forming composition” refers to components other than the solvent, and specific examples of the solid content include liquid crystal compounds, dichroic substances, and the other components described above.
[0258] Other components that may be contained in the light absorption anisotropic film-forming composition are the same as other components that may be contained in the light absorption anisotropic film of the present invention.
[0259] The content of other components relative to the total solid content mass of the light absorbing anisotropic film-forming composition is preferably the same as the content of other components relative to the total mass of the light absorbing anisotropic film of the present invention.
[0260] <Polymerization initiator>
[0261] The light-absorbing anisotropic film-forming composition preferably contains a polymerization initiator. The polymerization initiator is not particularly limited, but is preferably a photosensitive compound, that is, a photopolymerization initiator.
[0262] As the photopolymerization initiator, various compounds can be used without particular limitation. Examples of the photopolymerization initiator include α-carbonyl compounds (U.S. Patent No. 2367661, U.S. Patent No. 2367670), acyloin ethers (U.S. Patent No. 2448828), α-hydrocarbon-substituted aromatic acyloin compounds (U.S. Patent No. 2722512), polynuclear quinone compounds (U.S. Patent No. 3046127 and U.S. Patent No. 2951758), combinations of triaryl imidazole dimers and p-aminophenyl ketones (U.S. Patent No. 3549367), and polynuclear quinones (U.S. Patent No. 3549367). Specification), acridine and phenazine compounds (Japanese Patent Publication No. 60-105667, U.S. Patent No. 4239850), oxadiazole compounds (U.S. Patent No. 4212970), o-acyl oxime compounds (Japanese Patent Publication No. 2016-27384
[0065] ) and acylphosphine oxide compounds (Japanese Patent Publication No. 63-40799, Japanese Patent Publication No. 5-29234, Japanese Patent Publication No. 10-95788 and Japanese Patent Publication No. 10-29997), etc.
[0263] As such a photopolymerization initiator, a commercially available product can be used, and examples thereof include Irgacure 184, Irgacure 907, Irgacure 369, Irgacure 651, Irgacure 819, Irgacure OXE-01, and Irgacure OXE-02 manufactured by BASF Corporation.
[0264] The polymerization initiator may be used alone or in combination of two or more.
[0265] When the light absorbing anisotropic film-forming composition contains a polymerization initiator, the content of the polymerization initiator is preferably 0.01 to 30 parts by mass, and more preferably 0.1 to 15 parts by mass, relative to 100 parts by mass of the total of the dichroic substance and the liquid crystal compound in the light absorbing anisotropic film-forming composition. When the content of the polymerization initiator is 0.01 parts by mass or more, the durability of the light absorbing anisotropic film becomes good, and when the content of the polymerization initiator is 30 parts by mass or less, the orientation degree of the light absorbing anisotropic film becomes better.
[0266] <Solvent>
[0267] From the viewpoint of workability and the like, the light absorption anisotropic film-forming composition preferably contains a solvent.
[0268] Examples of the solvent include ketones (e.g., acetone, 2-butanone, methyl isobutyl ketone, cyclopentanone, and cyclohexanone), ethers (e.g., dioxane, tetrahydrofuran, tetrahydropyran, dioxolane, tetrahydrofurfuryl alcohol, and cyclopentyl methyl ether), aliphatic hydrocarbons (e.g., hexane), alicyclic hydrocarbons (e.g., cyclohexane), aromatic hydrocarbons (e.g., benzene, toluene, xylene, and trimethylol), halogenated carbons (e.g., dichloromethane, chloroform, dichloroethane, dichlorobenzene, and chlorotoluene), esters (e.g., ethyl acetate, ethyl acetate, etc.), and ethers. Organic solvents such as methyl acetate, ethyl acetate and butyl acetate, diethyl carbonate, etc.), alcohols (such as ethanol, isopropanol, butanol and cyclohexanol, etc.), cellosolves (such as methyl cellosolve, ethyl cellosolve and 1,2-dimethoxyethane, etc.), cellosolve acetates, sulfoxides (such as dimethyl sulfoxide, etc.), amides (such as dimethylformamide and dimethylacetamide, N-methylpyrrolidone, N-ethylpyrrolidone, 1,3-dimethyl-2-imidazolidinone, etc.) and heterocyclic compounds (such as pyridine, etc.), and water. These solvents may be used alone or in combination of two or more.
[0269] Among these solvents, organic solvents are preferably used, and halogenated carbons or ketones are more preferably used because the effects of the present invention are more excellent.
[0270] When the light absorbing anisotropic film-forming composition contains a solvent, the content of the solvent is preferably 80 to 99 mass %, more preferably 83 to 98 mass %, and further preferably 85 to 97 mass % based on the total mass of the light absorbing anisotropic film-forming composition.
[0271] [Method for producing anisotropic light absorption film]
[0272] The method for manufacturing a light absorbing anisotropic film of the present invention comprises:
[0273] a coating film forming step of coating a composition including a liquid crystal compound, a dichroic substance and a solvent to form a coating film;
[0274] A first heating step of heating the coating film at a temperature higher than the melting point of the dichroic substance;
[0275] a cooling step of cooling the coating film subjected to the first heating step; and
[0276] The second heating step is to heat the coating film subjected to the cooling step at a temperature that is 15° C. or more lower than the phase transition temperature of the liquid crystal compound from the crystalline state to the liquid crystal state.
[0277] According to the method for producing a light absorption anisotropic film of the present invention, the above-mentioned light absorption anisotropic film of the present invention can be easily obtained.
[0278] Hereinafter, each step will be described.
[0279] <Coating film forming step>
[0280] The coating film forming step is a step of forming a coating film by applying a composition containing a liquid crystal compound, a dichroic substance, and a solvent.
[0281] The composition used in the coating film forming step is the same as the above-mentioned light absorption anisotropic film-forming composition, and therefore the description thereof is omitted.
[0282] Here, the solvent contained in the composition is the same as the solvent described in the above-mentioned composition for forming anisotropic light-absorbing films, and is preferably a solvent capable of dissolving the liquid crystal compound and the dichroic substance contained in the composition. Here, the solvent capable of dissolving the liquid crystal compound and the dichroic substance means that the mass of the liquid crystal compound dissolved in 100 g of the solvent at 25° C. is 0.5 g or more, and the mass of the dichroic substance dissolved in 100 g of the solvent is 0.1 g or more.
[0283] Examples of the method for applying the composition include known methods such as roll coating, gravure printing, spin coating, wire bar coating, extrusion coating, direct gravure coating, reverse gravure coating, die coating, spray coating, and inkjet.
[0284] In this step, the coating film is preferably applied on the alignment film.
[0285] (Oriented Film)
[0286] The alignment film can be provided by the following methods: such as friction treatment of the film surface of an organic compound (preferably a polymer), oblique evaporation of an inorganic compound, formation of a layer with microgrooves, or accumulation of organic compounds (e.g., ω-tricosanoic acid, dioctadecylmethylammonium chloride, methyl stearate, etc.) based on the Lamb-Blodgett method (LB film). In addition, alignment films that generate alignment functions by imparting an electric field, imparting a magnetic field, or irradiating light are also known. Among them, in the present invention, from the viewpoint of easy control of the pretilt angle of the alignment film, an alignment film formed by friction treatment is preferred, and from the viewpoint of uniformity of the orientation, a photo-aligned film formed by irradiating light is also preferred.
[0287] (1) Rubbing treatment of oriented film
[0288] The polymer material used in the oriented film formed by rubbing treatment is described in many documents and is available in many commercial products. In the present invention, polyvinyl alcohol or polyimide and its derivatives are preferably used. Regarding the oriented film, reference can be made to the description on page 43, line 24 to page 49, line 8 of International Publication No. 2001 / 88574A1. The thickness of the oriented film is preferably 0.01 to 10 μm, more preferably 0.01 to 1 μm.
[0289] (2) Photo-alignment film
[0290] As a photo-alignment material for an alignment film formed by light irradiation, there are records in a plurality of documents, etc. In the present invention, as preferred examples, for example, Japanese Patent Publication No. 2006-285197, Japanese Patent Publication No. 2007-76839, Japanese Patent Publication No. 2007-138138, Japanese Patent Publication No. 2007-94071, Japanese Patent Publication No. 2007-121721, Japanese Patent Publication No. 2007-140465, Japanese Patent Publication No. 2007-156439, Japanese Patent Publication No. 2007-133184, Japanese Patent Publication No. 2009-109831, Japanese Patent No. 3883848, Japanese Patent No. 4151746 can be cited. The present invention further comprises azo compounds, aromatic ester compounds described in Japanese Patent Application Laid-Open No. 2002-229039, maleimide and / or alkenyl-substituted nadic imide compounds having a photo-alignment unit described in Japanese Patent Application Laid-Open No. 2002-265541 and Japanese Patent Application Laid-Open No. 2002-317013, photo-crosslinkable silane derivatives described in Japanese Patent No. 4205195 and Japanese Patent No. 4205198, photo-crosslinkable polyimides, polyamides or esters described in Japanese Patent Translation No. 2003-520878, Japanese Patent Translation No. 2004-529220 or Japanese Patent No. 4162850. More preferably, the present invention further comprises azo compounds, photo-crosslinkable polyimides, polyamides or esters.
[0291] The photo-alignment film formed of the above-mentioned material is irradiated with linearly polarized light or non-polarized light to produce the photo-alignment film.
[0292] In this specification, "linearly polarized light irradiation" and "non-polarized light irradiation" refer to operations for causing a photo-alignment material to produce a photoreaction. The wavelength of the light used varies depending on the photo-alignment material used, and is not particularly limited as long as it is a wavelength required for the photoreaction. The peak wavelength of the light used in the photo-irradiation is preferably 200nm to 700nm, and more preferably ultraviolet light with a peak wavelength of 400nm or less.
[0293] The light source used in the light irradiation can include commonly used light sources, such as tungsten lamps, halogen lamps, xenon lamps, xenon flash lamps, mercury lamps, mercury-xenon lamps and carbon arc lamps, various lasers [for example, semiconductor lasers, helium-neon lasers, argon ion lasers, helium-cadmium lasers and YAG (yttrium aluminum garnet) lasers], light emitting diodes, and cathode ray tubes.
[0294] As a method of obtaining linearly polarized light, a method using a polarizing plate (e.g., an iodine-based polarizing plate, a dichroic polarizing plate, and a wire grid polarizing plate), a method using a prism element (e.g., a Glan-Thomson prism) or a reflective polarizer using the Brewster angle, or a method using light emitted from a laser light source having polarized light can be adopted. In addition, a filter or a wavelength conversion element can be used to selectively irradiate only light of a desired wavelength.
[0295] When the irradiated light is linearly polarized light, the method of irradiating the light vertically or obliquely to the surface of the alignment film from the upper surface or the back surface of the alignment film is adopted. The incident angle of the light varies depending on the photo-alignment material, but is preferably 0 to 90° (vertical), preferably 40 to 90°.
[0296] In the case of non-polarized light, the non-polarized light is irradiated obliquely toward the alignment film, and the incident angle is preferably 10 to 80°, more preferably 20 to 60°, and further preferably 30 to 50°.
[0297] The irradiation time is preferably 1 minute to 60 minutes, more preferably 1 minute to 10 minutes.
[0298] When patterning is required, a method of irradiating light using a photomask a number of times required for patterning or a method of writing a pattern by laser scanning can be adopted.
[0299] The coating film forming step may include a drying process, whereby components such as the solvent can be removed from the coating film.
[0300] The drying treatment may be performed by leaving the coating film at room temperature for a predetermined period of time (for example, natural drying), or by at least one of heating and blowing air.
[0301] The temperature of the drying treatment is preferably lower than the melting point of the dichroic substance, for example, 25 to 110° C. The drying time is, for example, 200 seconds or less.
[0302] The dichroic substance contained in the composition may be oriented by the above-mentioned coating film forming step. For example, when the solvent is removed from the coating film by drying the coating film, the dichroic substance contained in the coating film may be oriented.
[0303] <First heating step>
[0304] The first heating step is a step of heating the coating film at a temperature higher than the melting point of the dichroic substance. As a result, the dichroic substance contained in the coating film is oriented, and the degree of orientation of the obtained light absorption anisotropic film becomes higher.
[0305] In the present invention, the melting point of the dichroic substance (hereinafter, also referred to as "T1" in degrees Celsius) refers to the melting peak temperature in a DSC curve obtained by heating the dichroic substance using a differential scanning calorimeter (DSC). The measurement conditions based on DSC are a measurement temperature range of -50 to 170 degrees Celsius and a heating rate of 10 degrees Celsius / minute.
[0306] When the coating film contains a plurality of dichroic substances, T1 above represents the melting point of the dichroic substance having the highest melting point among all the dichroic substances contained in the coating film (composition).
[0307] The heating temperature of the coating film in the first heating step (hereinafter also referred to as the "first heating temperature") is a temperature higher than T1. From the viewpoint of achieving a better degree of orientation of the light-absorbing anisotropic film, it is preferably above (T1+5)°C, more preferably above (T1+8)°C, and even more preferably above (T1+10)°C.
[0308] From the viewpoint of reducing damage to the coating film, the first heating temperature is preferably (T1+80)°C or lower, and more preferably (T1+50)°C or lower.
[0309] The heating time is preferably 1 to 300 seconds, more preferably 20 to 130 seconds.
[0310] <Cooling process>
[0311] The cooling step is a step of cooling the coating film subjected to the first heating step.
[0312] In the cooling and fixing, the coating film is preferably cooled to about room temperature (20 to 25° C.). Thereby, the orientation of the dichroic substance contained in the coating film is further fixed, and the orientation degree of the obtained light absorption anisotropic film becomes higher. The cooling method is not particularly limited and can be implemented by a known method.
[0313] <Second heating step>
[0314] The second heating step is a step of heating the coating film subjected to the cooling step at a temperature 15° C. or more lower than the phase transition temperature of the liquid crystal compound from the crystalline state to the liquid crystal state.
[0315] At the heating temperature of the coating film in this step, the liquid crystal compound maintains a crystalline state, thereby limiting the movement of molecules of the dichroic substance that have not formed an association present in the film. It is speculated that the size of the association of the dichroic substance is suppressed from becoming too large, and the light absorption anisotropic film of the present invention that satisfies the above formula (1) can be obtained.
[0316] In the present invention, the phase transition temperature (hereinafter, also referred to as "T2" in degrees Celsius) of a liquid crystal compound from a crystalline state to a liquid crystal state represents the glass transition point in a DSC curve obtained by heating the liquid crystal compound using a differential scanning calorimeter (DSC). In addition, the measurement conditions based on DSC are a measurement temperature range of -50 to 170°C and a heating rate of 10°C / minute.
[0317] When the coating film contains a plurality of liquid crystal compounds, T2 indicates the phase transition temperature at which the liquid crystal compound with the largest content among all the liquid crystal compounds contained in the coating film (composition) changes from a crystalline state to a liquid crystal state.
[0318] The heating temperature of the coating film in the second heating step (hereinafter also referred to as "second heating temperature") is (T2-15)°C or lower, preferably (T2-25)°C or lower.
[0319] From the viewpoint of heat resistance, the second heating temperature is preferably (T2-60)°C or higher, and more preferably (T2-45)°C or higher.
[0320] The heating time is preferably 1 to 80 seconds, more preferably 30 to 70 seconds.
[0321] <Other Process>
[0322] The present production method may include a step of curing the light absorption anisotropic film after the second heating step (hereinafter also referred to as a “curing step”).
[0323] The curing step is performed, for example, by at least one of heating and light irradiation (exposure). Among them, the curing step is preferably performed by light irradiation.
[0324] The light source used for curing can use various light sources such as infrared rays, visible light or ultraviolet rays, but ultraviolet rays are preferred. In addition, ultraviolet rays may be irradiated while heating during curing, or ultraviolet rays may be irradiated through a filter that transmits only a specific wavelength.
[0325] Furthermore, the exposure may be performed in a nitrogen atmosphere. When the light absorption anisotropic film is cured by radical polymerization, the inhibition of polymerization by oxygen can be reduced, so the exposure is preferably performed in a nitrogen atmosphere.
[0326] The present manufacturing method may also include a step of heating the coating film after the first heating step and before the cooling step. The heating temperature of this step (hereinafter also referred to as "third heating temperature") is implemented at a temperature that does not satisfy the first heating temperature and the second heating temperature. For example, in the case where the first heating temperature>the second heating temperature, it is preferred to satisfy the relationship of the first heating temperature>the third heating temperature>the second heating temperature.
[0327] The present production method may include a step of cooling the coating film (light absorption anisotropic film) after the second heating step. This step is the same as the above-mentioned cooling step, and therefore its description is omitted.
[0328] [Laminated body]
[0329] The laminated body of the present invention comprises a substrate and the light absorption anisotropic film disposed on the substrate, and may comprise an alignment film between the substrate and the light absorption anisotropic film.
[0330] Hereinafter, each member constituting the laminated body of the present invention will be described.
[0331] 〔Base material〕
[0332] The substrate is preferably a transparent support. The transparent support refers to a support having a visible light transmittance of 60% or more, and the transmittance is preferably 80% or more, and more preferably 90% or more.
[0333] As the transparent support, a known transparent resin film, a transparent resin plate, a transparent resin sheet, etc. can be used, but there is no particular limitation.
[0334] As the transparent resin film, cellulose acylate film (for example, cellulose triacetate film (refractive index 1.48), cellulose diacetate film, cellulose acetate butyrate film, cellulose acetate propionate film), polyethylene terephthalate film, polyether sulfone film, polyacrylic resin film, polyurethane resin film, polyester film, polycarbonate film, polysulfone film, polyether film, polymethylpentene film, polyether ketone film, (meth)acrylonitrile film, etc. can be used.
[0335] Among them, a cellulose acylate film is preferred, which has high transparency, little optical birefringence, is easy to produce, and is generally used as a protective film for a polarizing plate, and a triacetate cellulose film is more preferred.
[0336] The thickness of the substrate is usually 20 to 100 μm.
[0337] In the present invention, it is particularly preferred that the substrate is a cellulose ester film and the film thickness is 20 to 70 μm.
[0338] 〔Light absorption anisotropic film〕
[0339] The light absorption anisotropic film of the present invention is as described above, and therefore the description thereof will be omitted.
[0340] The thickness of the light absorption anisotropic film is not particularly limited, but is preferably 100 to 8000 nm, more preferably 300 to 5000 nm.
[0341] 〔Oriented film〕
[0342] The alignment film (alignment layer) is as described above, and therefore the description thereof is omitted.
[0343] 〔λ / 4 plate〕
[0344] One of the preferred embodiments of the laminate of the present invention includes an embodiment having a light absorption anisotropic film and a λ / 4 plate. Such a laminate is preferably used as a circular polarizing plate.
[0345] The λ / 4 plate is a plate having a λ / 4 function, and specifically, a plate having a function of converting linearly polarized light of a certain wavelength into circularly polarized light (or converting circularly polarized light into linearly polarized light).
[0346] For example, as a method in which the λ / 4 plate has a single-layer structure, specifically, a phase difference film in which a stretched polymer film or a light absorption anisotropic film with a λ / 4 function is provided on a support, etc., and as a method in which the λ / 4 plate has a multi-layer structure, specifically, a wide-band λ / 4 plate formed by stacking a λ / 4 plate and a λ / 2 plate can be mentioned.
[0347] The λ / 4 plate and the light absorption anisotropic film may be provided in contact with each other, or another layer may be provided between the λ / 4 plate and the light absorption anisotropic film. Examples of such a layer include an adhesive layer or bonding layer for ensuring adhesion, and a barrier layer.
[0348] Furthermore, the λ / 4 plate is preferably a positive A plate and the wavelength dispersion of the phase difference Re has an anti-dispersion wavelength dispersion. Here, the anti-dispersion wavelength dispersion means that Re(λ) and Rth(λ) become larger as the wavelength λ increases, and at this time, the phase difference Re(λ) satisfies the following formulas (1-1) and (1-2).
[0349] Formula (1-1): Re(450) / Re(550)<1.0
[0350] Formula (1-2): Re(650) / Re(550)>1.0
[0351] Here, Re(λ) and Rth(λ) represent the in-plane phase difference and the phase difference in the thickness direction at wavelength λ, respectively. Re(λ) and Rth(λ) are values measured at wavelength λ using AxoScan OPMF-1 (manufactured by Opto Science, Inc.). By inputting the average refractive index ((nx+ny+nz) / 3) and film thickness (d(μm)) into AxoScan, the slow axis direction (°), Re(λ)=(nx-ny)×d, and Rth(λ)=((nx+ny) / 2-nz)×d are calculated.
[0352] Furthermore, nx and ny are respectively the refractive indexes in the in-plane direction of the optical component. Generally, nx is the refractive index in the slow axis direction, and ny is the refractive index in the fast axis direction (i.e., the direction orthogonal to the slow axis). Furthermore, nz is the refractive index in the thickness direction. Regarding nx, ny and nz, for example, an Abbe refractometer (NAR-4T, manufactured by ATAGO CO., LTD.) can be used, and a sodium lamp (λ=589nm) can be used as a light source for measurement. Furthermore, in the case of measuring wavelength dependence, a multi-wavelength Abbe refractometer DR-M2 (manufactured by ATAGO CO., LTD.) can be used to measure in combination with an interference filter. Furthermore, the values of the polymer handbook (JOHN WILEY & SONS, INC) and various optical film catalogs can also be used.
[0353] The positive A plate refers to an optical component whose refractive indexes nx, ny, and nz satisfy the following formula (1-3): In the formula (1-3), "≈" includes not only the case where the two are completely the same, but also the case where the two are substantially the same.
[0354] Formula (1-3): nx>ny≈nz
[0355] As a material used in preparing the λ / 4 plate, a surface modifier can be mentioned. Preferred embodiments of the surface modifier are the same as the surface modifier that can be contained in the above-mentioned light absorption anisotropic film.
[0356] 〔Barrier layer〕
[0357] The laminate of the present invention preferably has a substrate and a light absorption anisotropic film and also has a barrier layer.
[0358] Here, the barrier layer is also referred to as a gas barrier layer (oxygen barrier layer), and has a function of protecting the polarizing element of the present invention from gases such as oxygen in the atmosphere, moisture, compounds contained in adjacent layers, and the like.
[0359] Regarding the barrier layer, for example, reference can be made to paragraphs
[0014] to
[0054] of Japanese Patent Publication No. 2014-159124, paragraphs
[0042] to
[0075] of Japanese Patent Publication No. 2017-121721, paragraphs
[0045] to
[0054] of Japanese Patent Publication No. 2017-115076, paragraphs
[0010] to
[0061] of Japanese Patent Publication No. 2012-213938, and paragraphs
[0021] to
[0031] of Japanese Patent Publication No. 2005-169994.
[0360] [Image display device]
[0361] The image display device of the present invention preferably includes the above-mentioned light absorption anisotropic film of the present invention or the above-mentioned laminated body of the present invention, and further includes a display element.
[0362] The display element is preferably disposed on the polarizer side of the laminate (ie, the side opposite to the substrate). The polarizer and the liquid crystal cell may be laminated via a known adhesive layer or pressure-sensitive adhesive layer.
[0363] The display element used in the display device of the present invention is not particularly limited, and examples thereof include a liquid crystal cell, an organic electroluminescent (hereinafter, abbreviated as "EL") display panel, and a plasma display panel.
[0364] Among them, a liquid crystal cell or an organic EL display panel is preferred. That is, as the display device of the present invention, a liquid crystal display device using a liquid crystal cell as a display element or an organic EL display device using an organic EL display panel as a display element is preferred.
[0365] Image display devices include those that are thin and can be formed into a curved surface. The light absorption anisotropic film used in the present invention is thin and easily bendable, and therefore can also be preferably used in image display devices having a curved display surface.
[0366] In addition, some image display devices have a pixel density exceeding 250 ppi and can display high-definition images. The light absorption anisotropic film used in the present invention can also be preferably used in such high-definition image display devices without generating interference ripples.
[0367] 〔Liquid crystal display device〕
[0368] As an example of the display device of the present invention, a liquid crystal display device preferably includes the above-mentioned light absorption anisotropic film of the present invention and a liquid crystal cell. More preferably, a liquid crystal display device includes the above-mentioned laminate of the present invention (excluding the λ / 4 plate) and a liquid crystal cell.
[0369] In the present invention, among the polarizing elements provided on both sides of the liquid crystal cell, the laminate of the present invention is preferably used as the polarizing element on the front side, and more preferably used as the polarizing elements on the front and back sides.
[0370] Hereinafter, the liquid crystal cell constituting the liquid crystal display device will be described in detail.
[0371] <Liquid crystal unit>
[0372] The liquid crystal cell used in the liquid crystal display device is preferably a VA (Vertical Alignment) mode, an OCB (Optically Compensated Bend) mode, an IPS (In-Plane-Switching) mode, or a TN (Twisted Nematic) mode, but is not limited thereto.
[0373] In a TN mode liquid crystal cell, rod-shaped liquid crystal molecules are substantially horizontally aligned when no voltage is applied, and further twisted at 60 to 120 degrees. TN mode liquid crystal cells are most commonly used as color TFT liquid crystal display devices and are described in many documents.
[0374] In a VA mode liquid crystal cell, rod-shaped liquid crystal molecules are substantially aligned vertically when no voltage is applied. VA mode liquid crystal cells include, in addition to (1) a narrow VA mode liquid crystal cell in which rod-shaped liquid crystal molecules are substantially aligned vertically when no voltage is applied and substantially aligned horizontally when voltage is applied (described in Japanese Patent Publication No. 2-176625), (2) a VA mode multi-domain (MVA mode) liquid crystal cell in order to widen the viewing angle (described in SID97, Digest of tech. Papers (Collection of Papers) 28 (1997) 845), (3) a liquid crystal cell in which rod-shaped liquid crystal molecules are substantially aligned vertically when no voltage is applied and in which multi-domain orientation is twisted when voltage is applied (n-ASM mode) (described in the Collection of Papers of the Japanese Liquid Crystal Symposium 58-59 (1998)), and (4) a SURVIVAL mode liquid crystal cell (published at LCD International 98). Furthermore, it may be any of PVA (Patterned Vertical Alignment), optical alignment (Optical Alignment), and PSA (Polymer-Sustained Alignment). Details of these modes are described in Japanese Unexamined Patent Publication No. 2006-215326 and Japanese Translation of National Publication No. 2008-538819.
[0375] In the liquid crystal unit of the IPS mode, the liquid crystal compound is substantially parallel to the substrate, and the liquid crystal molecules are made to respond in a plane by applying an electric field parallel to the substrate surface. That is, when no electric field is applied, the liquid crystal compound is oriented in the plane. In the IPS mode, a black display is obtained when no electric field is applied, and the absorption axes of the upper and lower polarizers are orthogonal. In Japanese Patent Publication No. 10-54982, Japanese Patent Publication No. 11-202323, Japanese Patent Publication No. 9-292522, Japanese Patent Publication No. 11-133408, Japanese Patent Publication No. 11-305217, Japanese Patent Publication No. 10-307291, etc., a method of using an optical compensation sheet to reduce light leakage during black display in an inclined direction and improve the viewing angle is disclosed.
[0376] [Organic EL display device]
[0377] As an example of the display device of the present invention, i.e., an organic EL display device, for example, a preferred embodiment includes the above-mentioned laminate of the present invention (preferably including a λ / 4 plate) and an organic EL display panel in order from the visual recognition side. In this case, the laminate preferably includes a protective layer, a light absorption anisotropic film, an alignment film, and a λ / 4 plate in order from the visual recognition side.
[0378] The organic EL display panel is a display panel composed of an organic EL element in which an organic light emitting layer (organic electroluminescent layer) is sandwiched between electrodes (cathode and anode). The structure of the organic EL display panel is not particularly limited, and a known structure can be adopted.
[0379] Example
[0380] Below, the present invention is further described in detail according to embodiment.As long as do not depart from the gist of the present invention, then can suitably change the material, usage amount, ratio, processing content and processing step etc. shown in the following embodiment.Therefore, the scope of the present invention should not be interpreted restrictively by the embodiment shown below.
[0381] [Example 1]
[0382] [Production of transparent support]
[0383] The following composition was charged into a mixing tank and stirred to prepare a cellulose acetate solution to be used as a core layer cellulose acylate solution.
[0384]
[0385] Compound F
[0386] [Chemical formula 8]
[0387]
[0388] 10 parts by mass of the following matting agent solution was added to 90 parts by mass of the above core layer cellulose acylate solution to prepare a cellulose acetate solution to be used as an outer layer cellulose acylate solution.
[0389]
[0390]
[0391] After filtering the core layer cellulose acylate solution and the outer layer cellulose acylate solution with filter paper having an average pore size of 34 μm and a sintered metal filter having an average pore size of 10 μm, the three layers of the core layer cellulose acylate solution and the outer layer cellulose acylate solutions on both sides thereof are simultaneously cast from a casting port onto a drum (endless belt casting machine) at 20°C.
[0392] Next, the film on the roll was peeled off when the solvent content in the film was about 20% by mass, and both ends of the film in the width direction were fixed with tenter clips, and the film was dried while being stretched in the transverse direction at a stretching ratio of 1.1 times.
[0393] Thereafter, the obtained film was conveyed between rollers of a heat treatment device and further dried to prepare a transparent support having a thickness of 40 μm. This was referred to as a cellulose acylate film A1.
[0394] [Preparation of photo-alignment film B1]
[0395] The composition for forming a photo-alignment film described later was continuously coated on the cellulose acylate film A1 by a wire bar. The support body with the coated film was dried with warm air at 140° C. for 120 seconds, and then the coated film was irradiated with polarized ultraviolet light (using a 10 mJ / cm 2 The photo-alignment film was formed by ultra-high pressure mercury lamp (UHV lamp), and a TAC (triacetyl cellulose) film with a photo-alignment film was obtained. The thickness of the photo-alignment film was 0.25 μm.
[0396]
[0397] Polymer PA-1 (In the formula, the numerical value described in each repeating unit represents the content (mass %) of each repeating unit relative to all repeating units.)
[0398] [Chemical formula 9]
[0399]
[0400] Acid Generator PAG-1
[0401] [Chemical formula 10]
[0402]
[0403] Stabilizer DIPEA
[0404] [Chemical formula 11]
[0405]
[0406] [Preparation of light absorption anisotropic film C1]
[0407] A light absorption anisotropic film-forming composition 1 having the following composition was continuously applied onto the obtained photo-alignment film B1 using a wire bar to form a coating film (coating film forming step).
[0408] Next, the coating film was heated at 140°C for 15 seconds (first heating step), continued to be heated at 80°C for 5 seconds, and cooled to room temperature (23°C) (cooling step). Next, the coating film was heated at 55°C for 60 seconds (second heating step), and cooled to room temperature again.
[0409] Here, the melting point of the dichroic substance Dye-C1 is 120°C, the melting point of the dichroic substance Dye-C2 is 120°C, the melting point of the dichroic substance Dye-M1 is 120°C, and the melting point of the dichroic substance Dye-Y1 is 110°C. The melting points of the dichroic substances contained in the light-absorbing anisotropic film-forming composition 1 are all lower than the heating temperature of the first heating step (140°C).
[0410] The phase transition temperature (temperature at which the liquid crystal compound changes from the crystalline state to the liquid crystal state) of the liquid crystal compound L-1 having the largest content among the liquid crystal compounds contained in the composition is 85°C, which is 30°C higher than the heating temperature (55°C) of the second heating step.
[0411] The melting point of the dichroic substance (T1° C. mentioned above) and the phase transition temperature of the liquid crystal compound (T2° C. mentioned above) were measured by the above-mentioned method. The same applies to other examples described below.
[0412] Then, an LED (light emitting diode) lamp (central wavelength 365nm) was used at an illumination of 200mW / cm 2 The film was irradiated for 2 seconds under irradiation conditions of , thereby producing a light absorption anisotropic film C1 (polarizer) (thickness: 1.8 μm) on the photo-alignment film B1.
[0413] The transmittance of the light absorption anisotropic film C1 in the wavelength range of 280 to 780 nm was measured by a spectrophotometer, and the average visible light transmittance was 42%.
[0414] The absorption axis of the light absorption anisotropic film C1 is located in the plane of the light absorption anisotropic film C1 and is orthogonal to the width direction of the cellulose acylate film A1.
[0415]
[0416] Dichroic Material Dye-C1
[0417] [Chemical formula 12]
[0418]
[0419] Dichroic substance Dye-C2
[0420] [Chemical formula 13]
[0421]
[0422] Dichroic Material Dye-M1
[0423] [Chemical formula 14]
[0424]
[0425] Dichroic Material Dye-Y1
[0426] [Chemical formula 15]
[0427]
[0428] Liquid crystal compound L-1 (wherein the numerical values ("59", "15", "26") described in each repeating unit represent the content (mass %) of each repeating unit relative to all repeating units.)
[0429] [Chemical formula 16]
[0430]
[0431] Liquid crystal compound L-2
[0432] [Chemical formula 17]
[0433]
[0434] Adhesion Improver A-1
[0435] [Chemical formula 18]
[0436]
[0437] Surfactant F-1 (wherein the numerical value described in each repeating unit represents the content (mass %) of each repeating unit relative to all repeating units.
[0438] [Chemical formula 19]
[0439]
[0440] [Formation of oxygen barrier layer D1]
[0441] A coating liquid D1 having the following composition was continuously coated on the light absorbing anisotropic film C1 by a wire bar. Thereafter, by drying with warm air at 80° C. for 5 minutes, a laminated body having an oxygen barrier layer D1 of 1.0 μm thick made of polyvinyl alcohol (PVA) was obtained, that is, a laminated body CP1 having a cellulose acylate film A1 (transparent support), a photo-alignment film B1, a light absorbing anisotropic film C1, and an oxygen barrier layer D1 adjacent to each other in this order was obtained.
[0442]
[0443] Modified polyvinyl alcohol
[0444] [Chemical formula 20]
[0445]
[0446] [Production of TAC film with positive A plate]
[0447] The coating liquid E1 for forming a photo-alignment film having the following composition was continuously coated on the cellulose acylate film A1 using a wire bar. The support body with the coating film was dried with warm air at 140° C. for 120 seconds, and then the coating film was irradiated with polarized ultraviolet light (10 mJ / cm 2 , using an ultra-high pressure mercury lamp), thereby forming a photo-alignment film E1 with a thickness of 0.2 μm, and obtaining a TAC film with a photo-alignment film.
[0448]
[0449] Acid Generator CPI-110TF
[0450] [Chemical formula 21]
[0451]
[0452] Polymer PA-2
[0453] [Chemical formula 22]
[0454]
[0455] The composition F1 with the following composition was applied onto the photo-alignment film E1 using a bar coater. The coating formed on the photo-alignment film E1 was heated to 120° C. using hot air, then cooled to 60° C., and then irradiated with 100 mJ / cm 2 at a wavelength of 365 nm using a high-pressure mercury lamp in a nitrogen atmosphere. 2The coating film was irradiated with ultraviolet rays and then heated to 120°C while 500 mJ / cm 2 The coating film was irradiated with ultraviolet rays, thereby fixing the orientation of the liquid crystal compound, thereby producing a TAC film having a positive A plate F1.
[0456] The thickness of the positive A plate F1 is 2.5 μm, and Re(550) is 144 nm. In addition, the positive A plate satisfies the relationship Re(450)≤Re(550)≤Re(650). Re(450) / Re(550) is 0.82.
[0457]
[0458] Polymerizable liquid crystal compound LA-1 (tBu represents tert-butyl group)
[0459] [Chemical formula 23]
[0460]
[0461] Polymerizable liquid crystal compound LA-2
[0462] [Chemical formula 24]
[0463]
[0464] Polymerizable liquid crystal compound LA-3
[0465] [Chemical formula 25]
[0466]
[0467] Polymerizable liquid crystal compound LA-4 (Me represents methyl group)
[0468] [Chemical formula 26]
[0469]
[0470] Polymerization initiator PI-1
[0471] [Chemical formula 27]
[0472]
[0473] Leveling agent T-1
[0474] [Chemical formula 28]
[0475]
[0476] [Manufacturing of TAC film having positive C plate H1]
[0477] As the pseudo support, the above-mentioned cellulose acylate film A1 was used.
[0478] The cellulose acylate film A1 was passed through a dielectric heating roller at a temperature of 60° C. to raise the surface temperature of the film to 40° C., and then coated on one side of the film with a coating amount of 14 ml / m 2 An alkaline solution having the composition shown below was applied, heated to 110° C., and conveyed under a steam-type far-infrared heater manufactured by NORITAKE CO., LIMITED for 10 seconds.
[0479] Next, pure water (3 ml / m2) was applied to the membrane using a bar coater. 2 Next, after water washing with a jet coater and dehydration with an air knife were repeated three times, the film was conveyed in a drying zone at 70° C. for 10 seconds to be dried, thereby producing an alkali saponified cellulose acylate film A1.
[0480]
[0481]
[0482] The photo-alignment film-forming coating liquid G1 having the following composition was continuously coated on the alkali-saponified cellulose acylate film A1 using a #8 wire bar. The obtained film was dried with 60°C hot air for 60 seconds and further with 100°C hot air for 120 seconds to form a photo-alignment film G1.
[0483]
[0484] A coating liquid H1 for forming a positive C plate having the following composition was applied onto the photo-alignment film G1, and the obtained coating film was aged at 60° C. for 60 seconds and then heated at 70 mW / cm in air. 2 An air-cooled metal halide lamp (manufactured by EYE GRAPHICS Co., Ltd.) was used to irradiate 1000 mJ / cm 2 The orientation state was fixed by ultraviolet rays, thereby vertically aligning the liquid crystal compound, thereby producing a TAC film having a positive C plate H1 with a thickness of 0.5 μm.
[0485] The Rth(550) of the obtained positive C plate was -60 nm.
[0486]
[0487]
[0488] Liquid crystal compound LC-1
[0489] [Chemical formula 29]
[0490]
[0491] Liquid crystal compound LC-2
[0492] [Chemical formula 30]
[0493]
[0494] Vertical alignment liquid crystal compound agent S01
[0495] [Chemical formula 31]
[0496]
[0497] Compound B03
[0498] [Chemical formula 32]
[0499]
[0500] [Preparation of adhesive (adhesive layer)]
[0501] Next, an acrylic polymer was prepared according to the following steps.
[0502] In a reaction vessel equipped with a cooling tube, a nitrogen inlet tube, a thermometer and a stirring device, butyl acrylate (95 parts by mass) and acrylic acid (5 parts by mass) were polymerized by a solution polymerization method to obtain an acrylic acid ester polymer (NA1) having an average molecular weight of 2,000,000 and a molecular weight distribution (Mw / Mn) of 3.0.
[0503] Next, an acrylic adhesive was prepared with the following composition using the obtained acrylic polymer (NA1). The composition was applied to a separation film surface-treated with a silicone release agent using a die coater, dried at 90° C. for 1 minute, and irradiated with ultraviolet light (UV) under the following conditions, thereby obtaining the following acrylic adhesive N1 (adhesive layer N1). The composition and film thickness of the acrylic adhesive are shown below.
[0504] <UV irradiation conditions>
[0505] FUSION Co., Ltd.'s electrodeless lamp H bulb
[0506] Illuminance 600mW / cm 2 , light intensity 150mJ / cm 2
[0507] The UV illuminance and light quantity were measured using “UVPF-36” manufactured by EYE GRAPHICS COMPANY.
[0508]
[0509] (A) Multifunctional acrylic monomer: tri(acryloyloxyethyl)isocyanurate, molecular weight = 423, trifunctional type (manufactured by TOAGOSEI CO., LTD., product name "ARONIX M-315")
[0510] (B) Photopolymerization initiator: a mixture of benzophenone and 1-hydroxycyclohexyl phenyl ketone in a mass ratio of 1:1, "Irgacure 500" manufactured by Ciba Specialty Chemicals Co., Ltd.
[0511] (C) Isocyanate crosslinking agent: trimethylolpropane-modified toluene diisocyanate ("CORONATE L" manufactured by Nippon Polyurethane Industry Co., Ltd.)
[0512] (D) Silane coupling agent: 3-glycidyloxypropyltrimethoxysilane ("KBM-403" manufactured by Shin-Etsu Chemical Co., Ltd.)
[0513] [Preparation of UV Adhesive Layer-Forming Composition]
[0514] A UV adhesive layer-forming composition having the following composition was prepared.
[0515]
[0516] CPI-100P
[0517] [Chemical formula 33]
[0518]
[0519] [Preparation of laminated body CPAC1]
[0520] The above-mentioned UV adhesive layer-forming composition was used at 600 mJ / cm 2 The phase difference side of the TAC film having the positive A plate F1 and the phase difference side of the TAC film having the positive C plate H1 are bonded under UV irradiation. The thickness of the UV adhesive layer is 3 μm. In addition, the surfaces bonded by the UV adhesive layer are respectively subjected to corona treatment. Next, the photo-alignment film E1 and the cellulose acylate film A1 on the side of the positive A plate F1 are removed and used as a phase difference plate AC1. In addition, the layer structure of the phase difference plate AC1 is a positive A plate F1, a UV adhesive layer, a positive C plate H1, a photo-alignment film G1 and a cellulose acylate film A1.
[0521] Using the above-mentioned adhesive layer N1, the oxygen barrier layer D1 side of the above-mentioned laminate CP1 is bonded to the support side of the low-reflection surface film CV-LC5 (manufactured by Fujifilm Corporation). Next, only the cellulose acylate film A1 contained in the above-mentioned laminate CP1 is removed, and the removed surface and the positive A plate F1 side of the above-mentioned phase difference plate AC1 are bonded using the above-mentioned adhesive layer N1. Next, the optical orientation film G1 and the cellulose acylate film A1 on the positive C plate H1 side contained in the above-mentioned phase difference plate AC1 are removed to prepare the laminate CPAC1. At this time, the angle formed by the absorption axis of the light absorption anisotropic film C1 contained in the above-mentioned laminate CPAC1 and the slow axis of the positive A plate F1 is bonded to 45°. In addition, the layer structure of the stacked body CPAC1 is a low-reflection surface film CV-LC5, an adhesive layer N1, an oxygen barrier layer D1, a light absorption anisotropic film C1, a photo-alignment film B1, an adhesive layer N1, a positive A plate F1, a UV adhesive layer, and a positive C plate H1.
[0522] The GALAXY S5 manufactured by SAMSUNG with an organic EL display panel was disassembled, and the touch panel with a circular polarizer was peeled off from the organic EL display device, and the circular polarizer was further peeled off from the touch panel, thereby separating the organic EL display panel, the touch panel, and the circular polarizer. Then, the separated touch panel was again bonded to the organic EL display panel, and the positive C-plate H1 side of the laminate CPAC1 manufactured above was further bonded to the touch panel via the adhesive layer N1 manufactured above in a manner that does not enter the air, thereby manufacturing an organic EL display device.
[0523] [Example 2]
[0524] A laminate and an organic EL display device were produced in the same manner as in Example 1, except that the heating temperature in the second heating step in producing the light absorption anisotropic film was changed to 45°C.
[0525] [Example 3]
[0526] A laminate and an organic EL display device were produced in the same manner as in Example 1 except that the light-absorbing anisotropic film-forming composition 2 described below was used instead of the light-absorbing anisotropic film-forming composition 1 and the heating temperature in the second heating step was changed to 45°C.
[0527]
[0528] [Example 4]
[0529] A laminate and an organic EL display device were produced in the same manner as in Example 1 except that the light-absorbing anisotropic film-forming composition 3 described below was used instead of the light-absorbing anisotropic film-forming composition 1 and the heating temperature in the second heating step was changed to 45°C.
[0530] Here, the phase transition temperature (temperature at which the liquid crystal compound changes from a crystalline state to a liquid crystal state) of the liquid crystal compound L-2 is 75° C., which is 30° C. higher than the heating temperature (45° C.) in the second heating step.
[0531]
[0532] [Example 5]
[0533] [Formation of Orientation Film A]
[0534] After a long cellulose acylate film (TD80UL, manufactured by FUJIFILM Corporation) was passed through a dielectric heating roller at a temperature of 60° C. to raise the film surface temperature to 40° C., an alkali solution of the composition shown below was applied at a coating amount of 14 ml / m 2 using a bar coater. 2 The film was coated on the tape surface and conveyed under a steam-type far-infrared heater manufactured by NORITAKE CO., LIMITED heated to 110°C for 10 seconds. 2 Pure water was applied to the film, and then washing with water using a jet coater and dehydration using an air knife were repeated three times, and then the film was conveyed to a drying zone at 70° C. and dried for 10 seconds to prepare an alkali saponified cellulose acylate film (thickness: 80 μm).
[0535]
[0536]
[0537] The alkali saponified surface of the cellulose acylate film was continuously coated with the following alignment film coating solution A using a #14 wire bar. The coating film was then dried with 60°C hot air for 60 seconds and further with 100°C hot air for 120 seconds to obtain an alignment film A (thickness: 0.5 μm).
[0538]
[0539] Polyvinyl alcohol-1
[0540] [Chemical formula 34]
[0541]
[0542] [Production of optically anisotropic layer Q]
[0543] The oriented film A prepared as above was continuously subjected to a rubbing treatment. At this time, the length direction of the long strip film was parallel to the conveying direction, and the angle between the length direction of the film and the rotation axis of the rubbing roller was set to 45° (if the width direction of the film was set to 0° and the length direction of the film was set to 90°, when observed from the oriented film A side, with the width direction of the film as a reference, a positive value indicates a clockwise direction, and the rotation axis of the rubbing roller is 45°).
[0544] The optically anisotropic layer Q coating liquid containing the rod-shaped liquid crystal compound of the following composition was continuously coated on the oriented film A after the rubbing treatment by a #3.4 wire rod. The conveying speed (V) of the film was set to 26 m / min. In order to dry the solvent of the coating liquid and mature the orientation of the rod-shaped liquid crystal compound, the coating on the oriented film was heated with 85°C warm air for 80 seconds and UV irradiated at 75°C to fix the orientation of the liquid crystal compound, thereby forming an optically anisotropic layer Q. The thickness of the optically anisotropic layer Q was 1.2 μm. The average tilt angle of the long axis of the rod-shaped liquid crystal compound relative to the film surface was 0°, and it was confirmed that the liquid crystal compound was horizontally oriented relative to the film surface. In addition, the angle of the slow axis was orthogonal to the rotation axis of the rubbing roller. If the film width direction was set to 0° (the film length direction was set to 90°, and when observed from the optically anisotropic layer Q side, the film width direction was used as the reference, and the positive value was expressed as the clockwise direction.), the angle of the slow axis was -45°. The in-plane retardation of the optically anisotropic layer Q at a wavelength of 550 nm was 142 nm, and the optically anisotropic layer Q showed positive wavelength dispersion.
[0545]
[0546] [Chemical formula 35]
[0547]
[0548] Fluorine-containing compound (F-2): weight average molecular weight: 16400)
[0549] [Chemical formula 36]
[0550]
[0551] [Production of photo-alignment film B2]
[0552] The photo-alignment film-forming composition was continuously coated on the optically anisotropic layer Q using a wire bar. The support on which the coating film was formed was dried with 140° C. hot air for 120 seconds, and then the coating film was irradiated with polarized ultraviolet light (using a 10 mJ / cm 2 The photo-alignment film was formed by using an ultra-high pressure mercury lamp, and an optical anisotropic film with a photo-alignment film was obtained. The thickness of the photo-alignment film was 0.9 μm.
[0553] [Preparation of laminate X1]
[0554] Except that the TAC (triacetyl cellulose) film with a photo-orientation film is changed to an optically anisotropic film with a photo-orientation film, a laminate X1 having a cellulose acylate film, an orientation film A, an optically anisotropic layer Q, a photo-orientation film B2, a light absorption anisotropic film C1, and an oxygen barrier layer D1 formed in this order is obtained in the same manner as in Example 1.
[0555] [Production of laminate X2]
[0556] The oxygen barrier layer D1 side of the laminate X1 was bonded to the support side of a low-reflection surface film CV-LC5 (manufactured by Fujifilm Corporation) using the adhesive layer N1. Next, the cellulose acylate film and the orientation film A contained in the laminate X1 were removed to prepare a laminate X2. In addition, the layer structure of the laminate X2 is a low-reflection surface film CV-LC5, an adhesive layer N1, an oxygen barrier layer D1, a light absorption anisotropic film C1, a light orientation film B2, and an optical anisotropic layer Q.
[0557] The GALAXY S5 manufactured by SAMSUNG with an organic EL display panel was disassembled, and the touch panel with a circular polarizer was peeled off from the organic EL display device, and the circular polarizer was further peeled off from the touch panel, thereby separating the organic EL display panel, the touch panel, and the circular polarizer. Then, the separated touch panel was again bonded to the organic EL display panel, and the optical anisotropic layer Q side of the laminate X2 prepared above was further bonded to the touch panel via the adhesive layer N1 prepared above in a manner that does not enter the air, thereby preparing an organic EL display device.
[0558] [Comparative Example 1]
[0559] A laminate and an organic EL display device were produced in the same manner as in Example 1 except that the light absorption anisotropic film-forming composition 4 described below was used instead of the light absorption anisotropic film-forming composition 1 and the heating temperature in the second heating step was changed to 75°C.
[0560]
[0561] [Number of associated compounds]
[0562] By the above method, each light absorption anisotropic film of the examples and comparative examples was observed in cross section, and the lengths of the major axes of the selected 100 aggregates were measured to determine the number Na of aggregates A having a major axis length of less than 30 nm, the number Nb of aggregates B having a major axis length of 30 nm or more and less than 60 nm, and the number Nc of aggregates C having a major axis length of 60 nm or more. The results are shown in Table 1.
[0563] [Concentration of dichroic substance in light absorption anisotropic film]
[0564] Concentration of dichroic material in each light absorption anisotropic film of Examples and Comparative Examples (mg / cm 3 ), and the above method was used to measure the results. The results are shown in Table 1.
[0565] [ΔlogP]
[0566] The logP values of the dichroic substances and liquid crystal compounds contained in each light absorption anisotropic film of the Examples and Comparative Examples were measured by the above method, and the absolute value of the difference between the logP value of the dichroic substance and the logP value of the liquid crystal compound (ΔlogP) was obtained. In addition, when a plurality of dichroic substances or liquid crystal compounds were used, the largest value among the absolute values of the differences calculated from the logP values of the respective compounds was adopted as ΔlogP. The results are shown in Table 1.
[0567] [Evaluation test]
[0568] 〔Black contrast〕
[0569] The visual recognition and display quality of each organic EL display device of the embodiment and the comparative example were evaluated under bright light. Specifically, the display screen of the organic EL display device was set to black display, and the reflected light when the fluorescent light was reflected from the front was observed, and the black contrast was evaluated according to the following criteria. The results are shown in Table 1.
[0570] <Evaluation Criteria>
[0571] A: Black, no visual coloring, and low reflectivity.
[0572] B: Slightly visually colored, but low reflectivity
[0573] C: Slightly visually colored and high reflectivity
[0574] [Heat resistance]
[0575] Each organic EL display device of the embodiment and the comparative example was subjected to 500 hours of heat resistance test in an environment of 85°C and a relative humidity of less than 10%. Afterwards, the display screen of the obtained organic EL display device was set to black display, and the reflected light when the fluorescent light was reflected from the front was observed, and the heat resistance was evaluated according to the following criteria. The results are shown in Table 1.
[0576] <Evaluation Criteria>
[0577] A: Compared with the evaluation result of black contrast before the heat resistance test, it is black and the color is the same, and the change in reflectance is also the same
[0578] B: Compared with the evaluation result of black contrast before the heat resistance test, the coloring increased slightly, but the reflectance change was the same
[0579] C: Compared with the evaluation results of black contrast before the heat resistance test, coloring increased slightly and the reflectance change also increased
[0580] [Table 1]
[0581]
[0582] In Table 1, "the difference between the phase transition temperature of the liquid crystal compound and the second heating temperature (°C)" represents the value obtained by subtracting the heating temperature of the second heating step (the second heating temperature) from the phase transition temperature (the temperature at which the liquid crystal compound with the largest content in the composition changes from the crystalline state to the liquid crystal state).
[0583] As shown in Table 1, when a circular polarizing plate composed of a light absorption anisotropic film and a λ / 4 plate in which the number Nb of the aggregate B and the number Nc of the aggregate C satisfy the relationship of the above formula (1) (Nb>Nc) is applied to a display device, the black contrast is excellent (Example).
[0584] Furthermore, comparison of Examples 1 to 4 shows that when a light absorption anisotropic film (Examples 1 and 2) is used in which the number Nb of the aggregates B and the number Nc of the aggregates C satisfy the relationship of the above formula (2) (0.5×Nb>Nc), the black contrast is further improved.
[0585] Furthermore, the comparison of Examples 1 to 4 shows that when a light absorption anisotropic film having the number Na of the association complexes A of less than 20 is used (Examples 1 and 4), the heat resistance is more excellent.
[0586] [Example 6]
[0587] [Production of Moth Eye Mask 1]
[0588] Regarding the description of paragraphs
[0177] to
[0210] of International Publication No. 2018 / 180003, the substrate HC-1 with a hard coating layer was replaced with a PMMA film and bonded with a UV adhesive. Thus, a moth-eye film 1 having a structure of a moth-eye layer / UV adhesive layer / PMMA film was obtained.
[0589] (Production of Optical Laminated Body B0)
[0590] The optical laminate B0 is prepared by the following steps. As a linear polarization type reflective polarizer, a broadband dielectric multilayer film (3M Company brand name APF) is used. The phase difference plate AC1 is attached to one surface of the APF using the adhesive layer N1, and the optical alignment film G1 and the cellulose acylate film A1 on the positive C plate H1 side contained in the phase difference plate AC1 are peeled off. Thus, an optical laminate B0 consisting of a linear polarization type reflective polarizer (APF) / adhesive layer N1 / positive A plate F1 / UV adhesive layer / positive C plate is prepared.
[0591] [Production of optical laminate B1K10]
[0592] The APF side of the optical laminate B0 obtained above and the oxygen barrier layer D1 side of the laminate X1 were bonded together using an acrylic adhesive N1, and the cellulose acylate film and the oriented film A were removed. The laminate was stacked in such a way that the transmission axis of the APF was consistent with the transmission axis of the light absorption anisotropic film C1. Next, the adhesive layer N1 was applied to the positive C plate side. Thus, an optical laminate D1 consisting of adhesive layer N1 / positive C plate / UV adhesive layer / positive A plate F1 / adhesive layer N1 / linear polarization type reflective polarizer / adhesive layer N1 / oxygen barrier layer D1 / light absorption anisotropic film C1 / optical orientation film B2 / optical anisotropic layer Q was obtained.
[0593] (Fabrication of optical laminate B2K11 and pancake optical system)
[0594] For the optical laminate D1, the PMMA film side of the moth-eye film 1 is bonded to the optical anisotropic layer Q side using an acrylic adhesive N1. Thus, an optical laminate D2 consisting of adhesive layer N1 / positive C plate / UV adhesive layer / positive A plate F1 / adhesive layer N1 / linear polarization type reflective polarizer / adhesive layer N1 / oxygen barrier layer D1 / light absorption anisotropic film C1 / light alignment film B2 / optical anisotropic layer Q / adhesive layer N1 / PMMA film / UV adhesive layer / moth-eye layer is obtained. By using the optical laminate D2 instead of the wavelength plate 1005, reflective polarizer 1006 and absorption polarizer 1007 of the pancake optical system shown in Figure 5 of International Publication No. 2020 / 209354, it functions as a VR (Virtual Reality) application.
[0595] Explanation of symbols
[0596] P-light absorption anisotropic film, M-molecules (of the first dichroic substance), O-molecules (of the second dichroic substance), L-molecules (of the liquid crystal compound), G-aggregate, w-width, a-angle.
Claims
1. A light absorption anisotropic film comprising a liquid crystal compound and a dichroic substance, wherein: The dichroic substance forms an association complex, When 100 of the aggregates present on the cross section of the light absorption anisotropic film observed by a scanning transmission electron microscope are selected, and the number of aggregates B having a major axis length of 30 nm or more and less than 60 nm is defined as Nb, and the number of aggregates C having a major axis length of 60 nm or more is defined as Nc, the relationship between Nb and Nc satisfies the following formula (1): Nb>Nc (1).
2. The light absorption anisotropic film according to claim 1, wherein: The relationship between Nb and Nc satisfies the following formula (2): 0.5×Nb>Nc (2).
3. The light absorption anisotropic film according to claim 1, wherein: When 100 of the aggregates present on the cross section of the light absorption anisotropic film observed by a scanning transmission electron microscope are selected, and when the number of aggregates A having a major axis length of less than 30 nm is defined as Na, Na is 35 or less.
4. The light absorption anisotropic film according to claim 1, wherein: The concentration of the dichroic substance in the light absorption anisotropic film is 180 mg / cm 3 above.
5. The light absorption anisotropic film according to claim 1, wherein: The absolute value of the difference between the logP value of the liquid crystal compound and the logP value of the dichroic substance is 4.1 or more.
6. A method for producing a light-absorbing anisotropic film, which is the method for producing a light-absorbing anisotropic film according to any one of claims 1 to 5, comprising: a coating film forming step of coating a composition including a liquid crystal compound, a dichroic substance and a solvent to form a coating film; a first heating step of heating the coating film at a temperature higher than the melting point of the dichroic substance; a cooling step of cooling the coating film subjected to the first heating step; and The second heating step is to heat the coating film subjected to the cooling step at a temperature that is 15° C. or more lower than the phase transition temperature of the liquid crystal compound from the crystalline state to the liquid crystal state. 7 . A laminate comprising: a substrate and the light absorption anisotropic film according to claim 1 disposed on the substrate.
8. The laminate according to claim 7, wherein The invention further comprises a λ / 4 plate disposed on the light absorption anisotropic film. 9 . An image display device comprising the light absorption anisotropic film according to claim 1 . 10 . An image display device comprising the laminate according to claim 7 .
Citation Information
Patent Citations
Photosensitive compound containing trichloromethyl group, manufacture and photosensitive mixture
JP1985105667A
Acylphosphine oxide compound*its manufacture and its use
JP1988040799B2
Liquid crystal display device
JP1990176625A
Bisacylphosphine oxide, manufacture and use
JP1993029234B2
Phase difference plate and liquid crystal device provided with the same
JP1997292522A